A self-humidifying fuel cell hybrid power system suitable for passenger cars

By implementing self-humidification technology in fuel cell hybrid system, using multiple dimensions to accurately manage and control, the humidification module is removed, and the system volume and weight problems are solved, achieving a compact and lightweight design, suitable for passenger vehicle applications.

CN119208665BActive Publication Date: 2025-03-07安徽明天新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411690618.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In the existing fuel cell hybrid system, the humidification module in the air subsystem increases the system's volume, weight and cost, making it difficult to meet the compact space and lightweight needs of passenger cars.

Method used

By accurately managing and controlling the vehicle energy management strategy, auxiliary system control strategy, bipolar plate flow field selection and plating design, gas diffusion layer base layer selection and microporous layer design, catalytic layer design and proton exchange membrane selection, the self-humidification function of the fuel cell system is realized, the humidification module is removed, the system compactness is improved, and lightweight design is carried out on this basis.

Benefits of technology

It realizes the self-humidification function of the fuel cell system, simplifies the system structure, reduces volume and weight, improves the compactness and lightweight design of the system, and is suitable for passenger car application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208665B_ABST
    Figure CN119208665B_ABST
Patent Text Reader

Abstract

The present application discloses a self-humidifying fuel cell hybrid power system suitable for passenger cars, which relates to the field of passenger car power technology. The air subunit of the system does not contain a humidification module; the system achieves self-humidification of the proton exchange membrane by controlling the current density and temperature of the fuel cell stack; the present application accurately manages, controls, selects and designs in multiple dimensions such as vehicle energy management strategy, auxiliary system control strategy, bipolar plate flow field selection and coating design, gas diffusion layer substrate layer selection and microporous layer design, catalytic layer design and proton exchange membrane selection, so as to realize the self-humidification function of the fuel cell system, remove the humidification module and improve the compactness of the fuel cell system; and performs lightweight design on the basis of self-humidification to prepare a fuel cell system that meets the application scenarios of passenger cars, realize the compactness and lightweight design of the self-humidifying fuel cell, and make it more suitable for the application scenarios of passenger cars.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application belong to the field of passenger vehicle power technology, and relate to self-humidifying fuel cell hybrid power technology, and specifically to a self-humidifying fuel cell hybrid power system suitable for passenger vehicles. Background Art

[0002] Fuel cell vehicles usually use a fuel cell hybrid system of "fuel cell system and lithium-ion battery in parallel"; among them, the fuel cell system is the main power source, and the lithium-ion battery is the auxiliary power source. The lithium-ion battery is used to start the fuel cell system or to smooth the output power of the fuel cell system, thereby improving the energy efficiency of the entire fuel cell hybrid system.

[0003] First, due to the small size of passenger cars, every inch of space in the car is valuable, and passenger cars have very high requirements for the miniaturization of the power system to adapt to the compact space of passenger cars; second, passenger cars also often focus on the lightweight of the power system to improve the operating economy of the vehicle; therefore, the miniaturization and lightweight of the fuel cell hybrid system is one of the technical difficulties in the commercialization of hydrogen fuel cells in passenger car applications.

[0004] The fuel cell system consists of a fuel cell stack and auxiliary systems including water management. The water management of the fuel cell system refers to maintaining the water balance of each basic material in an optimal state, which not only maintains the proton conductivity of the proton exchange membrane, but also ensures the gas transmission capacity of the gas diffusion layer, and balances the proton conductivity and gas diffusion of the catalyst layer.

[0005] In the entire current density range, water balance is critical to the normal operation of the fuel cell system. In order to achieve a dynamic balance of water content in the fuel cell stack, the traditional solution is to add a humidification module to the air subsystem of the auxiliary system. The humidification module is Fig.10 As shown, however, the presence of a humidification module will increase the volume, weight and cost of the fuel cell system in a passenger car, which is very unfavorable for the promotion and use of the fuel cell system in passenger car applications. Therefore, how to provide a self-humidifying fuel cell hybrid system suitable for passenger cars that does not include a humidification module is a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention

[0006] The embodiments of the present application aim to solve at least one of the technical problems existing in the prior art; to this end, the embodiments of the present application propose a self-humidifying fuel cell hybrid power system suitable for passenger cars, which solves the above-mentioned problem through independent innovative self-humidification technology.

[0007] To achieve the above-mentioned object, the present application provides a self-humidifying fuel cell hybrid power system suitable for a passenger car, characterized in that it includes a lithium-ion battery unit, a fuel cell unit and a vehicle controller;

[0008] The fuel cell unit comprises a fuel cell stack, a hydrogen subunit and an air subunit, wherein the air subunit does not contain a humidification module; the fuel cell stack comprises a membrane electrode comprising a proton exchange membrane;

[0009] The system achieves self-wetting of the proton exchange membrane by controlling the current density and temperature of the stack;

[0010] The number and size of membrane electrodes in the stack are adapted to the power requirements of the on-board operating conditions of the passenger car to meet the self-wetting of the proton exchange membrane. The vehicle controller is used to manage the hybrid power output of the fuel cell unit and the lithium-ion battery unit.

[0011] Furthermore, the current density range of the stack that achieves self-wetting of the proton exchange membrane is called the current density window; the current density window value range is 0.1-1.8A / cm 2 The temperature range of the stack that achieves self-wetting of the proton exchange membrane is called the temperature window; the numerical range of the temperature window is 65-80°C.

[0012] Furthermore, the thickness of the proton exchange membrane is 6-10 μm; the numerical range of the ion exchange equivalent of the proton exchange membrane is 790-1075 g / mol; the effective area of ​​the stack is 273 cm 2 330 sections of membrane electrode.

[0013] Furthermore, the membrane electrode also includes a catalyst layer and a gas diffusion layer; the catalyst layer has a gradient hydrophobicity, and the hydrophobicity of the catalyst layer gradually increases in the direction away from the proton exchange membrane; the gas diffusion layer has a base layer, and the small pores and large pores on the base layer are bimodal distribution; the small pores and large pores are connected pores, the large pores are micron-sized pores with strong hydrophobicity, and the small pores are nanometer-sized pores with weak hydrophobicity; a microporous layer with a pore size gradient distribution is prepared on the base layer of the gas diffusion layer to form a derivative structure with gradient hydrophobicity.

[0014] Furthermore, the fuel cell stack also includes a bipolar plate, which is made of pure titanium and is progressively formed based on a uniform voltage coil magnetic pulse to form a cathode flow field and an anode flow field, and is laser welded; a graphite carbon surface layer is provided on the surface of the bipolar plate, and a nano C / TiC composite coating is formed on the graphite carbon surface layer in combination with vacuum heat treatment.

[0015] Furthermore, the cathode flow field in the bipolar plate adopts a straight-through cross-variable flow field; and the anode flow field in the bipolar plate adopts a corrugated constant cross-section flow field.

[0016] Furthermore, the vehicle controller is used to manage the hybrid power output of the fuel cell unit and the lithium-ion battery unit, including: the vehicle controller performs the hybrid power output of the fuel cell unit and the lithium-ion battery unit through a power following strategy, and the power following strategy is that the vehicle controller adjusts the power distribution of the fuel cell system and the lithium-ion battery according to the bus power demand of the vehicle and the charge state of the lithium-ion battery, and mainly uses the fuel cell to meet the power demand of the load, and the difference is supplemented or absorbed by the lithium-ion battery, so that the fuel cell system works in the best efficiency range; the best efficiency range is [lower power limit, upper power limit], and the method for determining the lower power limit and the upper power limit is:

[0017] According to the "power-efficiency" characteristic curve of the fuel cell unit, the optimal efficiency value is determined by considering the mass flow rate of hydrogen, and the power lower limit and power upper limit of the fuel cell unit are determined when the optimal efficiency value is attenuated by 10% to 15%.

[0018] Furthermore, the lithium-ion battery unit presets an upper limit value SOC of the lithium-ion battery state of charge SOC max and the lower limit of SOC SOC min , the target value SOC of the lithium-ion battery state of charge SOC mid It is the median of the upper limit value of the state of charge SOC of the lithium-ion battery and the lower limit value of the SOC;

[0019] By detecting the real-time value of the state of charge (SOC) of the lithium-ion battery re , estimate the maximum discharge power that the lithium-ion battery cell can currently release and the maximum charging power that it can currently absorb;

[0020] Lithium-ion battery state of charge SOC real-time value SOC re The deviation coefficient α is obtained using the following formula:

[0021] α=[0.5×(SOC max +SOC min )-SOC re ] / [0.5×(SOC max -SOC min )],

[0022] By limiting -1≤α≤1, the load slope and unloading efficiency of the fuel cell unit, the charging power of the lithium-ion battery unit, and the initial value of the state of charge SOC of the lithium-ion battery unit are set.

[0023] Furthermore, the power following strategy includes: (1) when the power demand of the bus exceeds the maximum power that the lithium-ion battery can currently release, the fuel cell unit is turned on; (2) the real-time value SOC of the lithium-ion battery at the current moment reLess than or equal to the lower limit of SOC min , the fuel cell unit is turned on; (3) During regenerative braking, the feedback power of the bus is greater than the current SOC real-time value SOC of the lithium-ion battery re The corresponding charging demand, the fuel cell unit shuts down; (4) During regenerative braking, the feedback power of the bus is less than the current SOC real-time value SOC of the lithium-ion battery re Corresponding to the charging demand, the fuel cell unit supplements the remaining power; (5) If the bus demand power is less than the fuel cell unit power, the bus charges the lithium-ion battery; (6) If the bus demand power is greater than the fuel cell unit power, the lithium-ion battery unit releases power to the bus.

[0024] Further, the fuel cell unit supplements the remaining power in the following manner:

[0025] (a) When α ≥ 0, the fuel cell unit does not need to supplement the surplus power;

[0026] (b) When α<0, the residual power value supplemented by the fuel cell unit is "the smaller of A and B". A is the difference between the bus feedback power and the maximum charging power that the lithium-ion battery is currently estimated to be able to absorb. B is the product of the SOC deviation coefficient α and the charging power of the lithium-ion battery.

[0027] (c) When SOC re <SOC min , and the supplementary surplus power value is between the power lower limit and the power upper limit of the fuel cell unit. At this time, the supplementary surplus power value is the power upper limit of the fuel cell unit. At the same time, the loading slope and unloading slope of the supplementary surplus power value meet the slope limit requirements.

[0028] Compared with the prior art, the beneficial effects of the embodiments of the present application are:

[0029] In order to remove the humidification module of the air subsystem in the prior art and carry out lightweight design on this basis, the embodiment of the present application provides a self-humidifying fuel cell hybrid system suitable for passenger cars, which performs precise management, control, selection and design in multiple dimensions such as vehicle energy management strategy, auxiliary system control strategy, bipolar plate flow field selection and coating design, gas diffusion layer substrate layer selection and microporous layer design, catalytic layer design and proton exchange membrane selection, so as to realize the self-humidification function of the fuel cell system, remove the humidification module, and improve the compactness of the fuel cell system; and carries out lightweight design on the basis of self-humidification, prepares a fuel cell system that meets the application scenarios of passenger cars, realizes the compactness and lightweight design of the self-humidifying fuel cell, and makes it more suitable for the application scenarios of passenger cars. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 This is a diagram of the execution architecture of the vehicle energy management in the embodiment of the present application;

[0032] Figure 2 This is a distribution diagram of the pore size-specific pore volume of the gas diffusion layer substrate in the embodiment of the present application;

[0033] Figure 3 This is a scanning electron microscope image of a microporous layer of a gas diffusion layer in an embodiment of the present application;

[0034] Figure 4 A top view of the cathode flow field of the bipolar plate in an embodiment of the present application;

[0035] Figure 5 This is a schematic diagram of the outward inclination of the flow channel in the embodiment of the present application;

[0036] Figure 6 A schematic diagram of a bipolar plate anode flow field in an embodiment of the present application;

[0037] Figure 7 A groove bank diagram of the anode flow field of the bipolar plate in the embodiment of the present application;

[0038] Figure 8 A schematic diagram of the structure of a nano C / TiC composite coating in an embodiment of the present application;

[0039] Fig. 9 This is a diagram of the fuel cell system architecture in an embodiment of the present application;

[0040] Fig.10 A schematic diagram of the working principle of the traditional solution involved in this application;

[0041] Fig.11 This is a schematic diagram of stamping of a cathode plate and an anode plate in an embodiment of the present application;

[0042] Fig.12 Schematic diagram of a hydrogen mixing tube in a hydrogen circuit in an embodiment of the present application. DETAILED DESCRIPTION

[0043] The technical solutions of the embodiments of the present application will be described clearly and completely in combination with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments in the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the embodiments of the present application.

[0044] See also Fig.10 As mentioned in the background technology, the humidification module of the air subsystem (humidifier, multiple auxiliary pipes, multiple auxiliary solenoid valves) will increase the number of components of the fuel cell air subsystem, causing the air subsystem to be complicated. In addition, the presence of the humidification module will increase the volume, weight and cost of the fuel cell system, which is very unfavorable for the promotion and use of the fuel cell system in passenger car applications.

[0045] In order to solve the above technical problems, the embodiments of the present application provide a solution to accurately manage, control, select and design in multiple dimensions such as vehicle energy management strategy, auxiliary system control strategy, bipolar plate flow field selection and coating design, gas diffusion layer substrate layer selection and microporous layer design, catalyst layer design and proton exchange membrane selection, so as to ensure good hydration of the proton exchange membrane, appropriate water content of the catalyst layer and suitable drainage capacity of the gas diffusion layer, optimize the water management capacity of the fuel cell stack, efficiently utilize the water generated by the electrochemical reaction of the fuel cell, realize the rationality of the water content distribution at different positions of the membrane electrode, realize the self-humidification function of the fuel cell system, remove the humidification module, simplify the fuel cell system, and improve the compactness of the fuel cell system; and carry out lightweight design based on self-humidification to prepare a fuel cell system that meets the application scenarios of passenger cars.

[0046] In an embodiment of the present application, a self-humidifying fuel cell hybrid power system suitable for a passenger car includes a fuel cell unit, a lithium-ion battery unit, and a vehicle controller; the fuel cell unit includes a stack, a hydrogen subunit, and an air subunit, wherein the air subunit does not contain a humidification module; the stack has a membrane electrode including a proton exchange membrane; the system achieves self-wetting of the proton exchange membrane by controlling the current density and temperature of the stack; the number and size of the membrane electrode in the stack are adapted to the power requirements of the on-board operating conditions of the passenger car to meet the self-wetting of the proton exchange membrane, and the vehicle controller manages the hybrid power output of the fuel cell unit and the lithium-ion battery unit. The vehicle energy management strategy is to reasonably allocate the power size and direction of each energy source (fuel cell system, lithium-ion battery) of the hybrid power system through the vehicle controller under the conditions of meeting the power required for vehicle driving and related constraints, thereby limiting the current density of the self-humidifying fuel cell system to 0.1A / cm 2 To 1.8A / cm 2 between.

[0047] The thermal balance and water balance inside the fuel cell are closely related and influence each other, so water management and thermal management are collectively referred to as water thermal management.

[0048] In an exemplary embodiment, the water thermal management subsystem of the auxiliary system control strategy limits the stack operating temperature of the self-humidifying fuel cell system to between 65°C and 80°C; on the one hand, it avoids excessive evaporation of internal water caused by the stack operating temperature exceeding the upper limit, causing excessive dehydration of the proton exchange membrane and the catalyst layer and a decrease in the concentration of the gas-phase reactant gas, thereby reducing the proton transfer capacity and the electrochemical reaction rate; on the other hand, considering the electrochemical reaction efficiency and the transmission rate of reverse diffusion water, the lower limit of the stack operating temperature is limited.

[0049] In an exemplary embodiment, on the one hand, by controlling the hydrogen flow rate of the hydrogen subsystem, the separation efficiency of the gas-water separator is fine-tuned (85% to 90%), and the remaining liquid water is used to humidify the hydrogen entering the stack. On the other hand, by controlling the hydrogen circulation pump of the hydrogen subsystem, the hydrogen circulation volume is increased according to the increase in the bus demand power, thereby further improving the humidification of the hydrogen entering the stack.

[0050] In an exemplary embodiment, the temperature control of the intercooler in the air subsystem is strengthened, the intercooler is connected to the auxiliary heat dissipation subsystem, and the temperature of the auxiliary heat dissipation subsystem is controlled between 50° C. and 55° C. to suppress the evaporation of water at the air inlet.

[0051] In an exemplary embodiment, inside the fuel cell stack, the flow direction of hydrogen is opposite to that of air, so as to humidify the cathode inlet by using the reverse diffusion water at the anode outlet.

[0052] In an exemplary embodiment, the thickness of the proton exchange membrane is 6-10 μm, the value range of the ion exchange equivalent is 790-1075 g / mol; the effective area of ​​the stack is 273 cm 2 330 membrane electrodes. The M765.08 composite proton exchange membrane is used, which is only 8.5μm thick. First, it has the characteristics of small amount of water required for self-wetting and short time required for self-wetting. Second, in the Gore-Select series of commercial proton exchange membranes, M765.08 has the largest reverse diffusion rate, which can alleviate the water concentration difference between the anode and cathode to the greatest extent. Third, M765.08 has a service life equivalent to that of the Gore-Select series. Fourth, the M765.08 composite proton exchange membrane has a medium ion exchange equivalent of 943g / mol, balancing the proton conductivity and water content.

[0053] In an exemplary embodiment, the cathode flow field adopts a straight-through cross-variable flow field; under high current density conditions, the air flow control of the air subsystem is used to enhance the cathode's under-ridge drainage capacity and under-ridge heat transfer capacity.

[0054] In an exemplary embodiment, the anode flow field adopts a corrugated constant cross-section flow field; under high current density conditions, the humidification effect, heat transfer capacity and drainage capacity of the anode are enhanced through the hydrogen flow control of the hydrogen subsystem.

[0055] In an exemplary embodiment, TA1 pure titanium is used to prepare bipolar plates to reduce the weight of the battery stack and make it more suitable for passenger car application scenarios; a magnetic pulse progressive forming process based on a uniform voltage coil is used to prepare anode plates and cathode plates; after the anode plates and cathode plates are prepared into double-polar plates by laser welding, "magnetron sputtering + heat treatment" is used to prepare "nano-carbon-titanium composite coating" on the surface of the bipolar plate. The nano-carbon-titanium composite coating not only has good corrosion resistance and conductivity, but also can regulate the hydrophobicity of the bipolar plate surface.

[0056] In an exemplary embodiment, the catalyst layer adopts a gradient hydrophobicity design, and the hydrophobicity of the catalyst layer gradually increases in the direction away from the proton exchange membrane, so as to balance the gas transmission and proton transmission of the catalyst layer; the pore size selection and surface treatment of the substrate layer are used to form gas-liquid two-phase partitioned transmission; and under high current density conditions, the additional capillary force brought about by the pore size difference of the interconnected pores in the substrate layer enhances the drainage capacity of the substrate layer; the microporous layer is designed with a gradient pore size, and under high current density conditions, the additional capillary force brought about by the pore size difference of the interconnected pores in the microporous layer enhances the drainage capacity of the microporous layer.

[0057] It should be noted that:

[0058] The reasons for limiting the current density operation window (vehicle energy management strategy), operating temperature operation window (auxiliary system control strategy), proton exchange membrane thickness (membrane electrode selection) and proton exchange membrane effective area (membrane electrode selection) in the embodiments of the present application are as follows:

[0059] The current density operation window of the self-humidifying fuel cell is set to 0.1A / cm based on factors such as "the amount of water generated at the cathode, the amount of water dragged by electroosmosis, the amount of water required for proton membrane self-wetting, and the time required for proton membrane self-wetting". 2 ~1.8A / cm 2 ; The embodiment of the present application presets a lower limit value of current density; on the one hand, when the area, thickness and stack operating temperature of the proton exchange membrane are constant, the greater the current density passing through the membrane, the shorter the time required for membrane self-wetting. When the current density increases to a certain value, the time required for membrane self-wetting will be sharply reduced, and the self-humidification function of the fuel cell system can be realized; on the other hand, inside the stack, the cathode catalyst layer undergoes an oxygen reduction reaction O2+4H + +4e -→2H2O, the amount of water generated is proportional to the current density of the stack; if the current density is too low, the amount of water generated is relatively small, and the self-wetting of the proton exchange membrane is more difficult. When the current density increases to a certain value, the amount of water generated reaches the minimum requirement for wetting the proton exchange membrane; when the proton exchange membrane area, the stack operating temperature and the current density are constant, the thinner the membrane thickness, the easier the entire membrane is wetted, and the less water is required for membrane wetting; therefore, a thinner proton exchange membrane can broaden the lower limit of the current density operation of the self-humidifying fuel cell system. The embodiment of the present application presets an upper limit of the current density; on the one hand, if the current density is too high, the cathode will generate too much water, and the auxiliary system will find it difficult to discharge the excess water in time, resulting in cathode flooding; on the other hand, if the current density is too high, the amount of electroosmotic drag water migrating from the anode to the cathode will be too large, further increasing the drainage burden of the auxiliary system and aggravating cathode flooding; both aspects will increase the concentration polarization of the cathode, thereby reducing the performance of the fuel cell system; finally, if the amount of electroosmotic drag water is too large, the anode will be seriously short of water, the anode proton transmission will be difficult, and the ohmic polarization of the anode will be increased; electroosmotic drag of hydrated cathode to generate water will cause the water concentration on the cathode side to be higher than the water concentration on the anode side. The concentration is high, resulting in reverse diffusion of water from the cathode to the anode. The rate of reverse diffusion depends on the thickness of the proton exchange membrane and the difference in water concentration on both sides. The thinner the membrane, the greater the reverse diffusion rate and the more reverse diffused water. The greater the difference in water concentration on both sides, the greater the reverse diffusion rate and the more reverse diffused water. Since a large difference in water concentration on both sides will increase the drainage burden of the auxiliary system and reduce the performance of the fuel cell system due to flooding of the cathode, choosing a thinner proton exchange membrane can increase the reverse diffusion rate and thereby increase the amount of reverse diffused water. Therefore, a thinner proton exchange membrane can broaden the upper limit of the current density operation of the self-humidifying fuel cell system.

[0060] The embodiment of the present application sets the stack operating temperature operating window of the self-humidifying fuel cell to 65°C to 80°C based on factors such as "current density operating window, evaporation of water in the stack and kinetic energy of reverse diffusion of water molecules"; if the stack operating temperature is too high, it will cause excessive evaporation of water, thereby causing excessive water loss in the proton exchange membrane, affecting the proton transport performance of the proton exchange membrane; if the stack operating temperature is too low, the kinetic energy of water molecules is too small, and the reverse diffusion rate is too low, thereby causing excessive drying of the anode catalyst layer of the membrane electrode, affecting the proton transport of the anode catalyst layer.

[0061] Based on factors such as "current density operating window and temperature operating window", the embodiment of the present application selects M765.08 composite proton exchange membrane to prepare a self-humidifying fuel cell system; regarding the thickness of the proton exchange membrane, a thinner proton exchange membrane (≤15μm) has the advantages of "high reverse diffusion rate, less water required for self-wetting and short time required for self-wetting"; the thinner the proton exchange membrane, the greater its reverse diffusion rate, the less water required for self-wetting and the shorter time required for self-wetting, but the proton exchange membrane cannot be too thin, otherwise the proton exchange membrane The hydrogen permeability, mechanical stability, chemical stability and thermal stability will be greatly reduced; therefore, the embodiment of the present application adopts the M765.08 composite proton exchange membrane to prepare the self-humidifying fuel cell system, and the thickness of the M765.08 composite proton exchange membrane is only 8.5μm (23℃; 50%RH); in contrast, the homogeneous proton exchange membrane is not suitable for the preparation of the self-humidifying fuel cell system, and NRE211 is the thinnest homogeneous proton exchange membrane, with a thickness of up to 25.4μm (23℃; 50%RH)>15μm.

[0062] The present invention adopts 273cm based on the factors of “current density operation window, temperature operation window, proton exchange membrane thickness, passenger car power demand and multi-physical field distribution”. 2 A proton exchange membrane is used to prepare a self-humidifying fuel cell system; within the technical framework of the embodiment of the present application, the area of ​​the proton exchange membrane is equivalent to the effective area of ​​the membrane electrode, and the effective area of ​​the membrane electrode is the area actually involved in the electrochemical reaction in the proton exchange membrane fuel cell; under the on-board power demand of a passenger car, if the effective area of ​​the membrane electrode is too small, then the stack will contain a larger number of membrane electrodes; the entire stack will be relatively long, and the distribution differences of the multi-physical fields (humidity field, structural mechanics field, mass transfer field and heat transfer field) between each membrane electrode will increase significantly; if the effective area of ​​the membrane electrode is too large, the distribution differences of the multi-physical fields (humidity field, electrochemical reaction field, mass transfer field, heat transfer field and electric field) inside each single membrane electrode will increase significantly; it should be noted that the "current density operating window, operating temperature operating window, proton exchange membrane thickness and proton exchange membrane area" will affect the self-humidification effect of the fuel cell system.

[0063] The embodiment of the present application finds a relative balance point or balance range among these four parameters or parameter ranges to achieve the self-humidification function; when the thickness and area of ​​the proton exchange membrane are selected, the performance of the self-humidifying fuel cell system will reach a level comparable to that of an external humidification fuel cell system (including a humidifier), thereby simplifying the fuel cell system and improving the compactness of the fuel cell system.

[0064] The proton exchange membrane requires a certain water content to maintain a high proton conductivity; the transmission of water molecules accompanying protons through the membrane is called electroosmotic drag, and the number of water molecules carried by each proton is called the electroosmotic drag coefficient, denoted as n; it should be noted that reverse diffusion also exists inside the membrane electrode, and n defined in the embodiment of the present application is the number of water molecules carried by each proton when there is no reverse diffusion; the amount of water migrating from the anode to the cathode is jointly affected by "current density and electroosmotic drag coefficient".

[0065] The electroosmotic drag coefficient is affected by the stack operating temperature, the ion exchange equivalent of the proton exchange membrane and the water content of the proton exchange membrane.

[0066] The electroosmotic drag coefficient n increases with the increase of the temperature of the fuel cell stack; the embodiment of the present application sets the operating temperature range of the self-humidifying fuel cell to 65°C to 80°C based on factors such as "current density operating window, evaporation amount of water in the fuel cell stack and kinetic energy of reverse diffusion of water molecules", and also takes the electroosmotic drag coefficient into consideration.

[0067] The electroosmotic drag coefficient n decreases with the increase of the ion exchange equivalent of the proton exchange membrane. On the one hand, although the proton exchange membrane with a high ion exchange equivalent has a small electroosmotic drag coefficient n, the proton transport capacity of the proton exchange membrane is also low; on the other hand, the proton transport capacity of the proton exchange membrane with a low ion exchange equivalent is high, but the electroosmotic drag coefficient n is also large. A large n will also lead to a relatively serious imbalance phenomenon of lack of hydration on the anode side and excess water on the cathode side of the fuel cell.

[0068] The M765.08 composite proton exchange membrane selected in the embodiment of the present application has a medium ion exchange equivalent of 943 g / mol; compared with proton exchange membranes with high ion exchange equivalent (1075 g / mol) and low ion exchange equivalent (790 g / mol), the ion exchange equivalent of M765.08 takes into account both the electroosmotic drag coefficient n and the proton transport capacity.

[0069] The electroosmotic drag coefficient increases with the increase of the water content of the proton exchange membrane; the water content of the embodiment of the present application is defined as: the average number of water molecules corresponding to each sulfonic acid group, denoted as λ; for the proton exchange membrane, the sulfonic acid group is a functional group that transfers protons. As a further solution of the embodiment of the present application, the catalytic layer is designed with gradient hydrophobicity, which indirectly affects the water content λ of the proton exchange membrane, so that it is kept within a suitable range, taking into account the electroosmotic drag coefficient and proton transfer capacity of the proton exchange membrane.

[0070] Inside the fuel cell system, the water concentration on the cathode side is higher than that on the anode side, forming a water concentration difference, driving water to diffuse back from the cathode side to the anode side; however, under the actual working state of the fuel cell, as the current density increases, the amount of water diffused in the reverse direction becomes increasingly lower than the amount of water dragged by electroosmosis, forming a net migration of water; when the current density increases to a certain value, water migrates from the anode side of the membrane to the cathode side, in order to avoid water imbalance between the anode side and the cathode side. This is another reason why the upper limit of the current density is preset in the embodiment of the present application; the M765.08 composite proton exchange membrane selected in the embodiment of the present application has a thickness of 8.5 μm (23°C; 50% RH), has a relatively large amount of reverse diffused water, and can widen the upper limit of the current density.

[0071] In the embodiment of the present application, in terms of vehicle energy management, the current density of the self-humidifying fuel cell system is limited to a range so that it remains within an operating window of 0.1 to 1.8 A / cm²; the execution architecture of the vehicle energy management is as follows Figure 1 As shown, the fuel cell hybrid system consists of a self-humidifying fuel cell system and a lithium-ion battery; the lithium-ion battery can effectively improve the dynamic stability of the hybrid system, has a more stable load tracking capability, plays a role in peak shaving and valley filling, smoothes the output power of the fuel cell, and reduces the impact of frequently changing working conditions on the durability of the fuel cell; when the vehicle is shut down or shut down at low temperature, the lithium-ion battery is required to assist in starting or cold starting the fuel cell system because the starting ability and cold starting ability of the fuel cell system are very poor.

[0072] The vehicle control unit (VCU) controls the power size and power direction of the self-humidifying fuel cell system and the lithium-ion power battery through energy management according to the bus power demand to achieve the drive of the whole vehicle; the whole vehicle energy management is that under the conditions of meeting the power required for vehicle driving and related constraints, the VCU uses a power following strategy to perform hybrid power output of the fuel cell unit and the lithium-ion battery unit. Within the electrical tightness window, the VCU adjusts the power size and direction of the fuel cell unit and the lithium-ion battery unit output according to the bus power demand of the passenger car and the charge state of the lithium-ion battery unit, so that the hybrid system achieves optimal performance parameters.

[0073] The present invention is based on a current density operation window of 0.1A / cm 2 Up to 1.8A / cm 2 A power following strategy is adopted. The power following strategy adjusts the power distribution of the fuel cell system and the lithium-ion battery according to the bus power demand of the whole vehicle and the state of charge (SOC) of the lithium-ion battery. The fuel cell is mainly used to meet the power demand of the load, and the difference is supplemented / absorbed by the lithium-ion battery. This allows the fuel cell system to operate in the optimal efficiency range and the fuel cell to operate in the operating window of the self-humidifying current density.

[0074] The implementation method of the power following strategy in the embodiment of the present application is:

[0075] The optimal efficiency range is determined based on the "power-efficiency" characteristic curve of the fuel cell system, taking into account the mass flow rate (g / s) of hydrogen to determine the optimal efficiency value. The power lower limit and power upper limit of the fuel cell system are determined when the optimal efficiency value decays by 10% to 15%. The current density value of the power lower limit is limited to 0.1A / cm 2 The current density value of the power upper limit is limited to 1.8A / cm 2 ; Estimate the maximum discharge power that the lithium-ion battery can currently release based on the current SOC of the lithium-ion battery; Estimate the maximum charging power that the lithium-ion battery can currently absorb based on the current SOC of the lithium-ion battery; The lithium-ion battery sets the SOC upper limit SOC max and SOC lower limit SOC min To prevent overcharge and over discharge of lithium-ion batteries, the upper limit SOC of lithium-ion batteries is taken. max and SOC lower limit SOC min Median SOC mid , defined as the SOC target value of the lithium-ion battery; according to the SOC target value and SOC real-time value SOC of the lithium-ion battery re , define the deviation coefficient α of SOC; the deviation coefficient is defined as:

[0076] α=[0.5×(SOC max +SOC min )-SOC re )] / [0.5×(SOC max -SOC min )], limit: -1≤α≤1; set the load slope and unloading efficiency of the fuel cell system; set the charging power of the lithium-ion battery; set the initial SOC of the lithium-ion battery;

[0077] Exemplarily, the power following strategy includes the following: (1) the power demand of the bus exceeds the maximum power that the lithium-ion battery can currently release, and the fuel cell system is turned on; (2) the SOC of the lithium-ion battery at the current moment is less than or equal to the SOC lower limit SOC min , the fuel cell system is turned on; (3) During regenerative braking, the feedback power of the bus is greater than the charging demand of the current SOC of the lithium-ion battery, and the fuel cell system is shut down; (4) During regenerative braking, the feedback power of the bus is less than the charging demand of the current SOC of the lithium-ion battery, and the fuel cell system supplements the remaining power; (5) The bus demand power is less than the fuel cell system power, and the bus charges the lithium-ion battery; (6) If the bus demand power is greater than the fuel cell system power, the lithium-ion battery releases power to the bus.

[0078] Exemplarily, in order to keep the SOC real-time value of the lithium-ion battery in (4) tending towards the SOC target value to prevent the lithium-ion battery from being overcharged, the fuel cell system supplementary surplus power is determined as:

[0079] (a) When α ≥ 0, the fuel cell system does not need to supplement the surplus power;

[0080] (b) When α<0, the fuel cell system supplements the remaining power value as “the smaller of A and B”; A is the difference between the bus feedback power and the maximum charging power that the lithium-ion battery is currently estimated to be able to absorb; B is the product of the SOC deviation coefficient and the charging power of the lithium-ion battery;

[0081] (c) When the lithium-ion battery SOC re <SOC min , and the supplementary surplus power value is between the lower power limit and the upper power limit of the fuel cell system. At this time, the supplementary surplus power value is the upper power limit of the fuel cell system. At the same time, the loading slope and unloading slope of the supplementary surplus power value meet the slope limit requirements.

[0082] The amount of water that migrates from the anode to the cathode through electroosmotic drag is proportional to the current density and the electroosmotic drag coefficient n. The current density operation window of the embodiment of the present application is 0.1A / cm 2 Up to 1.8A / cm 2 ; In order to control the electroosmotic drag coefficient n within a reasonable range, the embodiment of the present application also limits, selects and optimizes the upper limit of the operating temperature of the fuel cell stack.

[0083] In order to realize the self-humidification function, the temperature upper limit of the fuel cell system is set to 80° C. in the embodiment of the present application; in addition, the temperature upper limit of 80° C. also takes into account the proton transport capacity of the proton membrane and the catalyst layer and the ratio of the reaction gas in the gas phase.

[0084] In order to increase the amount of reverse diffusion water and alleviate the water concentration difference on both sides of the proton membrane as much as possible, the embodiment of the present application selects an M765.08 composite proton exchange membrane with a thickness of 8.5 μm (23°C; 50% RH) on the premise of meeting the service life of the proton exchange membrane;

[0085] On the one hand, due to the effect of electroosmotic drag, water migrates from the anode to the cathode; on the other hand, oxygen reduction reaction occurs on the cathode side to generate water; both reasons will cause the water concentration on the cathode side to be higher than that on the anode side, resulting in reverse diffusion of water from the cathode to the anode. The rate of reverse diffusion depends on the thickness of the proton exchange membrane and the concentration difference on both sides; as the current density increases, the amount of water diffused in the reverse direction becomes less and less than the amount of water dragged in the forward electroosmotic direction, which is why the upper limit of the current density (1.8A / cm 2 ) One of the reasons is that the current density is large (>1.8A / cm2 ), not only too much water is generated, but also too much water is dragged by electroosmosis. The reverse diffusion water is not enough to offset the water imbalance on both sides of the fuel cell, which causes the fuel cell system to lose its self-humidification function; the embodiment of the present application selects M765.08 composite proton exchange membrane based on the reverse diffusion rate, with a thickness of 8.5μm (23℃; 50%RH), which has a relatively large reverse diffusion water volume, at ≤1.8A / cm 2 The range of 100% can effectively offset the water imbalance on both sides of the fuel cell; and has a service life comparable to other Gore-Select series commercial proton membranes;

[0086] Exemplarily, the gas direction of the bipolar plate flow field of the fuel cell system adopts the method of counter-convection of hydrogen and air, that is, the flow direction of hydrogen in the anode flow field is opposite to the flow direction of air in the cathode flow field; air and hydrogen are counter-convected inside the fuel cell stack, and the circulation humidification of liquid water on the anode side and the cathode side is achieved through reverse diffusion, hydrogen flow and electroosmotic drag, so as to improve the uniformity of humidity distribution of the fuel cell;

[0087] For example, Fig. 9 As shown, the battery stack H 出 The hydrogen mixture (hydrogen + gas phase water) in the area first passes through the gas-liquid separator to reduce the liquid water to an appropriate content, and then passes through the hydrogen circulation pump to enter the fuel cell H 入 Area; On the one hand, in order to improve the reaction efficiency of the fuel cell and reduce the reaction time of the fuel cell during acceleration, H 入 The regional hydrogen supply is greater than the theoretical consumption of hydrogen, and the stoichiometric ratio is 1.1 to 1.3. If the hydrogen circulation is not done, the excess hydrogen will be directly discharged, which will cause a large amount of hydrogen waste, so the hydrogen circulation pump is very necessary. On the other hand, the tail exhaust hydrogen is mixed with liquid water. If the liquid water is not treated, it will cause too much liquid water to flow from the H 入 When the hydrogen mixture is entrained with too much liquid water, the separation efficiency of the gas-liquid separator used in the embodiment of the present application is 85% to 90%, and the separation efficiency is adjusted by the hydrogen flow rate. The larger the hydrogen flow rate, the higher the separation efficiency. The drain valve integrated into the gas-liquid separator has a control logic setting of "open 1 second / close 1 second" to achieve the function of automatic drainage. In order to reduce the burden of the hydrogen circulation pump, the embodiment of the present application uses a gas-liquid separator with a smaller flow resistance. In order to ensure hydrogen safety, the gas-liquid separator used in the embodiment of the present application also has good sealing performance and anti-icing function. The hydrogen flow rate of the hydrogen subsystem is controlled to adjust the liquid water content entering the hydrogen circulation pump with the hydrogen mixture.

[0088] For example; Fig. 9 As shown, under low current density conditions (close to 0.1A / cm 2 ), the electroosmotic drag effect is small and can be ignored, and the cathode O 出 The amount of water generated in the area is relatively small; it diffuses back to the anode H 入 The amount of liquid water in the area is relatively small. Liquid water is transported from H 入 Area area transfer to H 出 The amount of water in the area is relatively small; in order to improve the wettability of the anode hydrogen under low current density conditions; at the same time, the hydrogen demand of the fuel cell stack under low current density conditions on the vehicle is relatively low. At this time, the hydrogen flow rate is reduced through the hydrogen subsystem, and the separation efficiency of the gas-liquid separator is adjusted to nearly 85%, so that the liquid water content of the hydrogen mixed gas at the outlet of the gas-liquid separator is close to 15%. After being pressurized by the hydrogen circulation pump, it is evenly mixed with the pure hydrogen from the hydrogen injector and enters the H 入 area, improving H under low current density conditions 入 The wetness of the area; at the same time, the relatively hot hydrogen mixture (about 70 to 85°C) is mixed with the relatively cold hydrogen (30 to 40°C), which will liquefy part of the gas phase water in the hydrogen mixture. At the same time, the present invention adopts a "hydrogen mixing tube containing a Laval nozzle and a mixer" to further enhance the uniformity of liquid water humidification, and avoids the accumulation of a large amount of liquid water at the hydrogen inlet of the fuel cell stack through the forced spiral flow of hydrogen;

[0089] For example; Fig. 9 As shown, under high current density conditions (close to 1.8A / cm 2 ), although the cathode O 出 The area generates more water, which diffuses back to the anode H 入 There is more liquid water in the area; however, there is also a large electroosmotic drag effect; the reverse diffusion is opposite to the electroosmotic drag, and the electroosmotic drag effect is stronger than the reverse diffusion; hydrogen in high current density conditions, the hydrogen mixture contains more gas phase water, the relatively hot hydrogen mixture is mixed with the relatively cold hydrogen, and part of the gas phase water will liquefy to humidify the hydrogen at the anode inlet; at this time, the circulation volume of the hydrogen circulation pump is increased through the hydrogen subsystem, and the hydrogen mixing tube is combined to improve the uniformity of hydrogen humidification at the stack inlet, so as to improve the humidification of hydrogen at the anode inlet under high current density conditions; H 入 The humidification water in the area is transported to the H 出 The amount of water in the area; Increasing the circulation volume of the hydrogen circulation pump under high current density conditions is beneficial to improving the humidification of the entire anode side;

[0090] For example, Fig. 9As shown, the heat dissipation port of the intercooler is connected to the auxiliary heat dissipation subsystem; the self-humidifying fuel cell system designed in the embodiment of the present application has two heat dissipation systems, namely the auxiliary heat dissipation subsystem and the water thermal management subsystem; the auxiliary heat dissipation subsystem is used to dissipate heat for electrical components such as air compressor inverters, hydrogen circulation pump controllers, and fuel cell power converters; the water thermal management subsystem is used to dissipate heat for mechanical components such as fuel cells and air compressors; the coolant temperature of the auxiliary heat dissipation subsystem is relatively low, generally at 50°C to 55°C; the coolant temperature of the water thermal management subsystem is relatively high, generally at 65°C to 80°C; the intercooler is connected to the auxiliary heat dissipation subsystem, so that O 入 The air in the area remains at a lower temperature, suppressing O 入 The evaporation of liquid water in the regional air maintains O 入 Good humidification of the regional air; under low current density conditions (close to 0.1A / cm 2 The water heat management subsystem keeps the operating temperature of the fuel cell stack at close to 65°C. This is because the water production of the fuel cell stack is small at this time, which avoids excessive evaporation of liquid water in the fuel cell stack. The auxiliary heat dissipation subsystem keeps the air intake temperature of the intercooler at close to 50°C to enhance the heat dissipation of the O 入 Inhibition of regional liquid water evaporation; Under high current density conditions (close to 1.8A / cm 2 ), the water-heat management subsystem keeps the operating temperature of the fuel cell stack at nearly 80°C. This is because the fuel cell stack produces a lot of water at this time, and it is necessary to evaporate part of the liquid water, and rely on air and hydrogen exhaust to take away this part of the gaseous water. The air mixture is directly discharged from the fuel cell stack, and the hydrogen mixture is liquefied by the gas-liquid separator and discharged by the drain valve;

[0091] For example, under high current density conditions (current density close to 1.8A / cm 2 ), there is more water on the cathode side due to the electrochemical reaction and electroosmotic drag. In order to control O 出 Liquid water discharge in the area to avoid O 出 The cathode flow field of the bipolar plate of the present application embodiment adopts the following Figure 4 The straight-through cross-variable flow field shown in the figure; the air flow control of the air subsystem is used to adjust the discharge amount of the cathode liquid water; the flow channel in the cathode flow field has a narrow point in part of the flow channel, and the narrow points of adjacent flow channels are cross-arranged; Figure 4As shown in the figure, counting from top to bottom, the high-pressure variable diameter area of ​​the first flow channel is adjacent to the low-pressure straight-through area of ​​the second flow channel, and the high-pressure variable diameter area of ​​the second flow channel is adjacent to the low-pressure straight-through area of ​​the first flow channel; due to the different pressures of the air mixture (air + gas phase water) in the adjacent areas, the air mixture in the high-pressure variable diameter area will not only diffuse to the gas diffusion layer & catalyst layer directly below, but also cross the ridge (the area between the first flow channel and the second flow channel) into the low-pressure straight-through area, forming a forced convection effect; it can not only increase the flow rate of the air mixture, but also discharge the liquid water under the ridge through gas disturbance, avoiding the ridge Liquid water gathers in the gas diffusion layer & catalyst layer below, which can improve the water management ability under the fuel cell bank and the transmission efficiency of the air mixture; and the air subsystem adjusts the drainage capacity of the bipolar plate cathode flow field by controlling the air flow rate; the cathode flow field selected in the embodiment of the present application also has the advantage of a straight-through structure. Since the inlet and outlet distances of a single flow channel of the straight-through structure are relatively close, the liquid water in each flow channel is brought out by the convection of the air mixture, further enhancing the drainage capacity of the air subsystem to adjust the bipolar plate cathode flow field; in addition, the straight-through cross-variable flow field can balance "air diffusion, gas pressure loss and liquid water discharge";

[0092] In an exemplary embodiment, Figure 4 This is a top view of the cathode flow field. The walls on both sides of the flow channel Figure 4 It is not perpendicular to the paper, but is 93° to the paper (i.e. tilted outward by about 3°). Figure 5 shown.

[0093] For example, the hydrogen flow rate of the hydrogen subsystem is controlled to take into account both the humidification effect of the anode gas and the drainage capacity of the anode flow field; the bipolar plate anode flow field of the embodiment of the present application adopts the following method: Figure 6 The corrugated constant cross-section flow field shown in the figure; when the hydrogen mixture (hydrogen + gas phase water) flows through the corrugated bend, Dean vortices will be formed under the action of centrifugal force, which will strengthen the disturbance of the hydrogen mixture in the flow channel to change the steady flow state of the hydrogen mixture and increase the flow rate of the hydrogen mixture; after the flow rate is increased, the gas-liquid mixing effect and the liquid water discharge capacity can be enhanced; the hydrogen subsystem can take into account the hydrogen humidification effect and drainage capacity of the bipolar plate anode flow field; in addition, the corrugated constant cross-section flow field can balance the convection diffusion of the hydrogen mixture and the pressure loss of the hydrogen mixture;

[0094] In an exemplary embodiment, the bipolar plate flow field is as follows Figure 7 , as shown Figure 7 The arrow (green arrow) at A is the raised part, called the shore ridge, and the red line part of the arrow (red arrow) at B is the sunken part, called the groove;

[0095] The bipolar plate flow field is formed by ridges and grooves stacked alternately in a cycle.

[0096] Regarding the cathode flow field, the reaction heat is taken out by the air mixture; some areas of the cathode flow channel have narrow points, and the narrow points of adjacent flow channels are cross-arranged, and the air mixture can be pushed into the gas diffusion layer by the additional pressure generated by the narrow points. The inlet and outlet distances of a single straight flow channel are relatively close, and the heat in each straight flow channel can be taken out by the convection diffusion of the air mixture; when the air mixture pressures in adjacent flow channels are different, the air mixture in the high-pressure flow channel will not only diffuse to the gas diffusion layer & catalyst layer below the flow channel, but also can cross the bank ridge and enter the low-pressure flow channel; this forced convection effect can increase the flow rate of the air mixture, discharge the reaction heat under the bank ridge through the air mixture disturbance, avoid the heat accumulation of the gas diffusion layer & catalyst layer under the bank ridge, and improve the heat pipe capacity under the bank ridge of the fuel cell, balance the oxygen diffusion, heat transfer and air mixture pressure loss, which is conducive to the realization of the self-humidification function;

[0097] The anode flow field takes out the reaction heat through the flow path; the anode flow channel adopts a corrugated constant cross-section structure. When the hydrogen mixture flows through the corrugated bend, Dean vortices will be formed under the action of centrifugal force, which will strengthen the disturbance of the hydrogen mixture in the flow channel, thereby changing the steady flow state of the hydrogen mixture and enhancing the convective transmission of the hydrogen mixture; the flow field is composed of alternating flow channels and ridges, and the cathode ridge and the anode ridge form the middle cavity of the bipolar plate, with built-in coolant to control the operating temperature of the stack using the water thermal management subsystem; at the same time, due to the corrugated flow channel structure The structure will form a cross section with the middle cavity of the bipolar plate. The cross section can make the coolant in the adjacent middle cavity mix and convective heat transfer, which has the effect of enhancing heat transfer, can improve the hydrogen diffusion and humidification effect and heat pipe capacity of the fuel cell, and balance the diffusion and humidification of the hydrogen mixture, heat transfer and pressure loss of the hydrogen mixture; from the overall results, the cathode flow channel and the anode flow channel have the function of enhancing the mass transfer of the air mixture and the hydrogen mixture, which is conducive to the removal of liquid hydration and gas phase water through the reaction gas, and the proportion of gas phase water in the reaction gas is controlled by the temperature of the fuel cell stack;

[0098] The catalytic layer is composed of a carbon-supported platinum catalyst and an ion polymer; the catalyst requires a gas channel to provide a reaction gas, and the ion polymer requires a proton channel to transport protons; the catalytic layer of the embodiment of the present application adopts a gradient hydrophobicity design to maintain the water content of the catalytic layer within a suitable range to achieve a balance between the gas channel and the proton channel, taking into account both the reaction gas transmission and the proton transmission of the catalytic layer;

[0099] Since the cathode catalyst layer and the anode catalyst layer are the sites of oxygen reduction reaction and hydrogen oxidation reaction respectively, gradient hydrophobicity design is performed on the cathode catalyst layer and the anode catalyst layer according to the different water contents of the cathode catalyst layer and the anode catalyst layer of the fuel cell; since the water content of the cathode catalyst layer is relatively high, the cathode catalyst layer is designed into three cathode sub-catalyst layers; while the water content of the anode catalyst layer is relatively low, the anode catalyst layer is designed into two anode sub-catalyst layers; from the proton exchange membrane to the gas diffusion layer, the hydrophobicity of each sub-catalyst layer increases successively; the gradient hydrophobicity design is conducive to the partition water management of the catalyst layer, and under low current density conditions (less water is generated, close to 0.1A / cm 2 ), a portion of liquid water is retained by the relatively weaker hydrophobic area; under high current density conditions (more water is generated, close to 1.8A / cm 2 ), the additional driving force brought by the gradient hydrophobic structure formed by each sub-catalytic layer is used to enhance drainage; on the one hand, if the hydrophobicity of the carrier is weak, the hydrophobicity of the catalyst using the carrier is weak; on the other hand, if the ion exchange equivalent of the ion polymer is small, the number of hydrophilic sulfonic acid groups of the ion polymer is large, and the hydrophobicity of this type of ion polymer is weak; the gradient hydrophobicity of each sub-catalytic layer in the embodiment of the present application does not require additional hydrophobic agent, and the gradient hydrophobicity is formed only by the catalyst carrier and the type of ion polymer; the gradient hydrophobicity design of the catalyst layer is compatible with the gas transport and proton transport of the catalyst layer under low current density conditions and high current density conditions;

[0100] The gas diffusion layer is a medium for material transmission. The technical difficulty to be solved urgently is compatibility with high current density conditions (large amount of water generated, close to 1.8A / cm 2 ) and low current density conditions (less water is generated, close to 0.1A / cm 2 ) are "reactant gas transmission" and "liquid water transmission"; taking the cathode side of the proton exchange membrane fuel cell as an example, liquid water flows from the cathode catalyst layer to the cathode gas diffusion layer, which is opposite to the direction of oxygen diffusion; there are two transmission mechanisms of liquid water in the gas diffusion layer, namely the inverted tree mechanism and the finger flow channel mechanism; the embodiment of the present application uses carbon fiber paper with a bimodal pore size distribution to prepare the base layer. The embodiment of the present application selects commercial carbon fiber paper to meet the needs of the self-humidifying fuel cell system. This type of carbon fiber paper goes through three stages: "㈠ carbon fiber preparation, ㈡ carbon fiber papermaking and ㈢ carbon fiber paper graphitization"; the carbon fiber paper selected in the embodiment of the present application is prepared from two carbon fibers with different chopped lengths; such as Figure 2As shown in the figure, three different carbon fiber papers A, carbon fiber paper B and carbon fiber paper C are shown. The fiber paper A shown by the dotted line in the figure is selected in this embodiment. In the figure, Pore diameter refers to the diameter of the hole, which is used to describe the size of the pores inside the material; Specific pore volume refers to the total volume of all pores in a unit mass of material, which is called specific pore volume. The unit of specific pore volume cm³ / g reflects the relationship between volume (cm³) and mass (g), and is used to quantitatively compare the pore properties of different materials.

[0101] It can be calculated by the following formula:

[0102] Specific pore volume = total pore volume (Pore Volume, cm 3 ) / Mass, g

[0103] In the “pore size (μm)-specific pore volume (cm 3 / g)" distribution diagram, the pore size of the carbon fiber paper presents a bimodal distribution, which is composed of micron-scale macropores composed of long carbon fibers and nano-scale small pores composed of short carbon fibers; it should be noted that: the pore size range of the carbon fiber paper is named based on the pore size data of the gas diffusion layer in the embodiment of the present application, therefore, it is completely different from the definition standard for classifying "micropores", "mesopores" and "macroporos" specified by the International Union of Pure and Applied Chemistry; then, a polytetrafluoroethylene emulsion with a specific particle size is selected to perform a hydrophobic treatment on the carbon fiber paper to prepare a base layer; and then a microporous layer with a pore size gradient distribution is prepared on the base layer; not only does it have the original functions of the microporous layer (improving flatness, reducing contact resistance, improving pore size, and improving gas-liquid distribution), but it also enhances the liquid water transmission inside the microporous layer.

[0104] The improvement of the gas diffusion layer in the embodiment of the present application is "selecting a carbon fiber paper substrate with a bimodal pore size distribution, zoned hydrophobic treatment and gradient hydrophobic design of the microporous layer"; the carbon fiber paper substrate contains micron-sized macropores and nano-sized pores, and the substrate is subjected to zoned hydrophobic treatment in combination with a polytetrafluoroethylene hydrophobic agent of a specific size; by introducing polytetrafluoroethylene particles into the micron-sized macropores, these areas can be made highly hydrophobic, and the nano-sized pores cannot be entered by polytetrafluoroethylene particles, so they maintain a relatively weak hydrophobicity; at low current density (less water is generated, close to 0.1A / cm 2 ), the weakly hydrophobic areas of the nanopores help retain the liquid, thereby providing better wettability and liquid transfer, avoiding excessive water loss in the catalyst layer adjacent to the substrate layer, and maintaining the proton transport capacity of the catalyst layer; at high current density (more water is generated, close to 1.8 A / cm 2), the strongly hydrophobic areas of the micron-sized macropores help to repel liquids, thereby optimizing gas diffusion and transfer; under full current density conditions, the substrate layer prepared in the embodiment of the present application can achieve partitioned transmission of liquid hydrated reaction gas, avoiding interference caused by the opposite transmission directions of the two; in addition, under high current density conditions, the additional capillary force brought about by the pore size difference of the substrate layer through holes further enhances the drainage capacity of the carbon fiber paper substrate layer; therefore, the carbon fiber paper substrate layer prepared in the embodiment of the present application not only achieves partitioned transmission of reaction gas and liquid water under high current density conditions and low current density conditions, but also enhances the liquid water drainage capacity of the substrate layer under high current density conditions;

[0105] The gradient hydrophobicity design of the microporous layer is conducive to the stratified water management of the microporous layer. 2 ), a portion of liquid water is retained by the weakly hydrophobic sub-microporous layer, thus providing better wettability and liquid transfer; at high current density (more water is generated, close to 1.8A / cm 2 ), the strongly hydrophobic sub-microporous layer helps to repel liquid, thereby optimizing gas diffusion and transfer; in addition, under high current density conditions, the additional capillary force brought by the pore size gradient formed by each sub-microporous layer further enhances the drainage capacity of the gradient microporous layer; therefore, the microporous layer prepared on the carbon fiber paper in the embodiment of the present application is not only compatible with the transmission of reaction gas and liquid water under high current density conditions and low current density conditions, but also further enhances the liquid water drainage capacity of the microporous layer under high current density conditions;

[0106] The lightweight fuel cell system can effectively reduce energy consumption, thereby extending the cruising range of passenger cars; the lightweight fuel cell system helps to improve the acceleration performance of passenger cars. Lighter vehicles can accelerate faster at the same power, providing a better driving experience; the weight distribution of passenger cars has an important impact on handling performance. Reducing the weight of the fuel cell system helps to optimize the center of gravity and balance of the vehicle, and improve handling stability and flexibility; the embodiment of the present application uses TA1 commercial pure titanium to prepare the anode plate and the cathode plate. TA1 commercial pure titanium has extremely high specific strength and can significantly reduce weight while ensuring strength. At the same time, during the operation of the fuel cell, titanium ions have little effect on the Pt catalyst in the membrane electrode.

[0107] On the one hand, the yield strength of TA1 commercial pure titanium is about 100MPa higher than that of stainless steel, and the elongation is about 10% lower than that of stainless steel, which leads to a decrease in its forming performance; on the other hand, the low elastic modulus of TA1 commercial pure titanium (about 50% of that of stainless steel) will cause springback, resulting in fluctuations in the depth of the flow channel; these two reasons make it difficult to achieve the processing of titanium bipolar plates by traditional stamping forming processes; the embodiment of the present application adopts the process of "progressive forming based on uniform pressure coil magnetic pulse" to prepare cathode flow field and anode flow field on TA1 commercial pure titanium, and prepare cathode plates and oxygen plates respectively;

[0108] It should be noted that:

[0109] First of all, the "magnetic pulse progressive forming based on uniform voltage coil" technology is: the uniform voltage coil has the advantages of uniform electromagnetic force loading, high forming rate and high forming efficiency, and is particularly suitable for the forming of thin-walled square metal plates such as cathode plates and anode plates; the primary coil is connected to a pulse power supply, and the metal sheet maintains electrical contact with the copper conductive channel to form a loop, and the loop is placed on the periphery of the primary coil. When the switch of the pulse power supply is closed, the high-voltage capacitor of the pulse power supply will generate a pulse current and flow to the primary coil to form a coil current; the coil current will generate a changing magnetic field around the metal sheet and the conductive channel. According to the law of electromagnetic induction, an induced current will be generated inside the metal sheet and the conductive channel, that is, the workpiece current; under the condition of maintaining electrical contact, the workpiece current will form a loop and the direction is opposite to that of the coil current; according to Ampere's force law, conductors carrying currents in opposite directions will repel each other; therefore, the metal sheet will move away from the primary coil and deform under the action of the electromagnetic force of the workpiece current; due to the design of the uniform pressure coil, the pressure on the surface of the metal sheet is uniform, and high-precision processing can be achieved; the flow field structure of the die adopts a straight-through cross-variable flow field and a corrugated constant cross-section flow field to prepare the cathode plate and the oxygen electrode plate;

[0110] After the cathode plate and the anode plate are prepared, the embodiment of the present application uses laser welding to prepare the bipolar plate;

[0111] After completing the laser welding of the bipolar plate, the bipolar plate needs to be surface treated to improve the conductivity and surface hydrophobicity of the bipolar plate; the embodiment of the present application first uses a magnetron sputtering method to prepare a layer of "graphite carbon surface layer" on the surface of the TA1 material to improve the conductivity and hydrophobicity of the surface of the bipolar plate; graphite has good electrical conductivity, mainly because the carbon atoms between the graphite layers are combined with each other in sp² hybrid orbitals to form a large range of π bond electron clouds, and these freely moving π electrons provide good conductivity; the surface of the graphite carbon layer is relatively smooth and chemically inert, making it difficult to react chemically with water molecules; the surface energy of the graphite carbon layer is low, and it is not easy to adsorb water molecules. Water will form water droplets with high contact angles on its surface, thereby showing good hydrophobicity;

[0112] After the graphite carbon coating is prepared, a "nano C / TiC composite coating" is prepared in combination with vacuum heat treatment to improve the adhesion and corrosion resistance of the composite coating; during the vacuum heat treatment process, carbon atoms and titanium atoms obtain enough energy and begin to diffuse with each other, with carbon atoms diffusing into the interior of the titanium substrate and titanium atoms diffusing toward the carbon coating; the diffused carbon atoms and titanium atoms react chemically at the interface to generate TiC; as the reaction proceeds, TiC gradually forms and grows at the interface between the carbon coating and the titanium substrate, eventually forming a continuous TiC intermediate layer at the interface; the TiC intermediate layer is formed by Chemical bonding makes the bond between the carbon layer and the titanium substrate stronger. Compared with simple physical adsorption, chemical bonding has stronger bonding force. The TiC intermediate layer acts as a transition layer, which reduces the interface mismatch between carbon and titanium, reduces the interface stress, and improves the adhesion of the coating. Both the carbon coating and the TiC intermediate layer have good corrosion resistance and can effectively protect the titanium substrate from corrosion by corrosive media, thereby improving the durability of the bipolar plate. Vacuum heat treatment makes the composite coating structure of the bipolar plate denser, reduces pores and defects, and thus improves the stability and durability of the composite coating in harsh environments.

[0113] In an exemplary embodiment, the hydrogen tail gas generated by the system is circulated through the gas-water separator and the hydrogen circulation pump in sequence, and then enters the fuel cell stack through the "mixer built into the hydrogen mixing tube". Fig.12 As shown, the hydrogen from the hydrogen injector enters the hydrogen mixing tube from the hydrogen inlet, and the tail exhaust hydrogen from the hydrogen circulation pump enters the hydrogen mixing tube from the hydrogen water inlet; since the two airflows (hydrogen and tail exhaust hydrogen) are not directly mixed, the high-temperature tail exhaust hydrogen is avoided from directly mixing with the low-temperature hydrogen. Since the hydrogen flow rate is not strong at this time, it will cause liquefaction of gaseous water and aggregation of liquid water; the hydrogen mixing tube used in the present invention contains a Laval nozzle and a mixer, the hydrogen flows through the inner wall of the Laval nozzle, and the tail exhaust hydrogen flows through the outer wall of the Laval nozzle. After the two airflows are mixed, they will directly enter the mixer to form a forced spiral flow, which will enhance the disturbance of the hydrogen flow, not only enhance the uniform wetting effect of the hydrogen, but also avoid the large-scale aggregation of liquid water, and prevent the introduction of a large amount of liquid water into the hydrogen inlet of the fuel cell stack.

[0114] The present application further provides the following exemplary embodiments 1-7 and comparative example 1 as follows:

[0115] Example embodiment 1:

[0116] Since the M765.08 composite proton exchange membrane has a short self-wetting time, a small amount of water required for self-wetting, a large amount of reverse diffusion water, a medium ion exchange equivalent and a small proton transmission distance, the present application embodiment selects the M765.08 composite proton exchange membrane to prepare a membrane electrode suitable for a self-humidifying fuel cell system; the present application embodiment prepares a gradient hydrophobic catalytic layer on both sides of the M765.08 composite proton exchange membrane by spraying to obtain a catalyst coated membrane (Catalyst Coated Membrane, abbreviated as CCM); since CCM generally consists of three parts: a cathode catalyst layer, a proton exchange membrane and an anode catalyst layer, CCM is also written as 3CCM;

[0117] The cathode catalyst layer is designed to be composed of three layers. The hydrophobicity of the cathode catalyst layer increases from the proton exchange membrane to the cathode gas diffusion layer. The cathode sub-catalytic layers are denoted as C1, C2 and C3, and C represents the cathode catalyst layer. Among them, C1 is 2 μm thick and is close to the proton exchange membrane; C2 is 3 μm thick; C3 is 3 μm thick and is close to the cathode gas diffusion layer. Each cathode sub-catalytic layer uses a 40% mass fraction of carbon-supported platinum catalyst. The resin-support ratio of the cathode slurries C1S, C2S and C3S corresponding to each cathode sub-catalytic layer is 0.65, and S represents the slurry. The hydrophobicity gradient distribution of each cathode sub-catalytic layer is jointly regulated by the "carbon carrier and ionic polymer type". On the one hand, chemical modification is used. To regulate the hydrophobicity of the carbon carrier, the carbon-supported platinum catalyst is prepared by the impregnation reduction method, and then carbon-supported platinum catalysts with different hydrophobicity are prepared. The carbon-supported platinum catalysts corresponding to each sub-catalytic layer of the cathode are denoted as C1C, C2C and C3C, and the second C represents the catalyst; on the other hand, ionic polymers with different ion exchange equivalents are selected. The ion exchange equivalent is closely related to the number of sulfonic acid groups on the side chain. The main chain of the ionic polymer is hydrophobic, and the side chain of the ionic polymer is hydrophilic; ionic polymers with different ion exchange equivalents have different ratios of main chain to side chain, and then the hydrophilicity and hydrophobicity of the ionic polymer are regulated. The ionic polymers corresponding to each sub-catalytic layer of the cathode are denoted as C1P, C2P and C3P, and P represents the ionic polymer. The parameters of the hydrophobicity gradient catalytic layer of the cathode are shown in Table 1:

[0118] Table 1 Parameters of cathode hydrophobic gradient catalytic layer

[0119]

[0120] The anode catalyst layer is designed to be two layers. The hydrophobicity of the anode catalyst layer increases from the proton exchange membrane to the anode gas diffusion layer. The anode sub-catalyst layers are denoted as A1 and A2, and A represents the anode catalyst layer. A1 is 1 μm thick and is close to the proton exchange membrane. A2 is 3 μm thick and is close to the anode gas diffusion layer. Each anode sub-catalyst layer uses a 40% mass fraction of carbon-supported platinum catalyst. The resin-support ratio of the anode slurry A1S and A2S corresponding to each anode sub-catalyst layer is 0.65, and S represents the slurry. The hydrophobicity gradient distribution of each anode sub-catalyst layer is jointly regulated by the "carbon carrier and ionic polymer type". On the one hand, chemical modification is used to adjust The hydrophobicity of the carbon carrier is controlled, and the carbon-supported platinum catalyst is prepared by the impregnation reduction method, and then the carbon-supported platinum catalysts with different hydrophobicity are prepared. The carbon-supported platinum catalysts corresponding to each sub-catalytic layer of the anode are respectively denoted as A1C and A2C, where C represents the catalyst; on the other hand, ionic polymers with different ion exchange equivalents are selected. The ion exchange equivalent is closely related to the number of sulfonic acid groups on the side chain. The main chain of the ionic polymer is hydrophobic, and the side chain of the ionic polymer is hydrophilic; the ionic polymers with different ion exchange equivalents have different ratios of the main chain to the side chain, and then the hydrophilicity and hydrophobicity of the ionic polymer are regulated. The ionic polymers corresponding to each sub-catalytic layer of the anode are respectively denoted as A1P and A2P, where P represents the ionic polymer. The parameters of the hydrophobicity gradient catalytic layer of the anode are shown in Table 2:

[0121] Table 2 Parameters of the anode hydrophobic gradient catalytic layer

[0122]

[0123] Catalyst C1C 、 The platinum content of C2C, C3C, A1C and A2C is designed to be 40%; 、 The carriers of C2C, C3C, A1C and A2C are prepared from Ketjen Black EC-600JD through a series of material chemistry methods to adjust the hydrophobicity to different degrees;

[0124] First, Ketjen Black EC-600JD was placed in a graphitization furnace for heat treatment; the heat treatment conditions were: argon protection atmosphere, heating rate 4℃ / min, holding temperature 2700℃, holding time 8h, and argon protection continued after the holding was completed and the temperature was naturally cooled; after the natural cooling was completed, it was taken out to obtain graphite carbon with high hydrophobicity; then the graphite carbon and ethanol were mixed and ground on an XQM-4 planetary ball mill to increase the fineness of the graphite carbon in preparation for subsequent chemical regulation; the grinding conditions were: graphite The mixing mass ratio of carbon to ethanol is 1:10, the rotation speed is 480RPM, the revolution speed is 240RPM, and the grinding time is 1h; after the grinding process is completed, it is dried to remove the residual ethanol, and the dried graphite carbon is divided into five parts, recorded as C1C graphite carbon, C2C graphite carbon, C3C graphite carbon, A1C graphite carbon and A2C graphite carbon; finally, the five parts of graphite carbon are acid-treated with nitric acid solution to adjust the hydrophobicity, forming five batches of carbon carriers with different hydrophobicity; the conditions of the acid treatment are shown in Table 3;

[0125] Table 3 Acid treatment conditions

[0126]

[0127] After the acid treatment, the five samples were respectively cleaned and dried and sealed for storage; they were recorded as C1C carrier, C2C carrier, C3C carrier, A1C carrier and A2C carrier;

[0128] Catalysts C1C, C2C, C3C, A1C and A2C were prepared using a C1C carrier, a C2C carrier, a C3C carrier, an A1C carrier and an A2C carrier, respectively; it should be noted that the synthesis methods of catalysts C1C, C2C, C3C, A1C and A2C are the same, but the carrier materials they use are: a C1C carrier, a C2C carrier, a C3C carrier, an A1C carrier and an A2C carrier, respectively; for the convenience of description, in the catalyst preparation process of the embodiment of the present application, the C1C carrier, the C2C carrier, the C3C carrier, the A1C carrier and the A2C carrier are uniformly referred to as a carrier;

[0129] First, (CH3COO)4Pt [solution], carrier [powder] and ultrapure water are mixed in a material mass ratio of m [Pt]: m [carrier] = 2:3, m [carrier]: m [ultrapure water] = 1:10; (CH3COO)4Pt / carrier [paste] is formed by mechanical stirring; the paste is quickly placed in a -50℃ to -60℃ environment and frozen for 2h to 4h to obtain (CH3COO)4Pt / carrier [frozen paste]; the mixture is heated in a vacuum and -50℃ ~80 ℃, gradually increase the temperature and dry for 20h~24h to obtain (CH3COO)4Pt / carrier [powder]; reduce (CH3COO)4Pt / carrier [powder] in a hydrogen and nitrogen mixed atmosphere to obtain Pt / carrier [powder], and complete the preparation of the catalyst; the reduction temperature is 150 ℃~200 ℃, and the reduction time is 1h~2h; filter and clean the Pt / carrier [powder] with ultrapure water and dry it; the corresponding relationship between the carrier and the catalyst is shown in Table 4

[0130] Table 4 Correspondence between carrier and catalyst

[0131]

[0132] The catalytic layer is composed of a catalyst and an ion polymer; wherein the catalyst is carbon-supported platinum and the ion polymer is a perfluorosulfonic acid resin; the perfluorosulfonic acid resin is obtained by copolymerization of tetrafluoroethylene monomer and perfluoroene ether sulfonic acid monomer; the perfluorosulfonic acid resin has a hydrophobic polytetrafluoroethylene main chain skeleton and a hydrophilic sulfonic acid group side chain at the molecular level; according to the length of the sulfonic acid group side chain, commercial perfluorosulfonic acid resins can be divided into "long side chain perfluorosulfonic acid resins, medium side chain perfluorosulfonic acid resins and short side chain perfluorosulfonic acid resins", and the relative molecular masses of the ene ether monomers used to synthesize these three commercial perfluorosulfonic acid resins are 446g / mol, 380g / mol and 280g / mol, respectively; the short side chain perfluorosulfonic acid resin has a lower ion exchange equivalent and exhibits relatively weak hydrophobicity, and the long side chain perfluorosulfonic acid resin has a higher ion exchange equivalent The relatively strong hydrophobicity, the hydrophobicity of the medium side chain perfluorosulfonic acid resin is between the two; in order to form a synergistic hydrophilic and hydrophobic effect with the catalyst, the cathode sub-catalytic layer C1 uses catalyst C1C and short side chain perfluorosulfonic acid resin C1P, the cathode sub-catalytic layer C2 uses catalyst C2C and medium side chain perfluorosulfonic acid resin C2P, and the cathode sub-catalytic layer C3 uses catalyst C3C and long side chain perfluorosulfonic acid resin C3P; compared with the cathode, the anode has relatively less water content, the anode sub-catalytic layer A1 uses catalyst A1C and short side chain perfluorosulfonic acid resin A1P, and the anode sub-catalytic layer A2 uses catalyst A2C and medium side chain perfluorosulfonic acid resin A2P; it should be pointed out that: in the embodiment of the present application, A1P and C1P are the same resin, A2P and C2P are also the same resin, and the numbering is to distinguish whether the resin is on the cathode side or the anode side;

[0133] The slurry is composed of a catalyst, an ionic polymer, an alcohol and ultrapure water, wherein the catalyst and the ionic polymer are solutes, and the alcohol and ultrapure water are solvents; as for the solvent, the alcohol is preferably isopropanol, and the volume ratio of isopropanol to ultrapure water is 4:1; as for the solute, the mass ratio of the ionic polymer to the mass ratio of the catalyst carrier is 0.65:1; as for the slurry, the mass fraction of the solute is 1.7%; the detailed parameters of each slurry are listed in Table 5;

[0134] Table 5 Detailed parameters of each slurry

[0135]

[0136] After the slurry is prepared, it is dispersed. Each slurry uses the same dispersion production line and process parameters. First, the slurry is transferred to the pulper, and the power of the rod ultrasonic disperser of the pulper is set to 800W, the ultrasonic frequency is set to 20kHZ, the rotating stirring blade speed is set to 40r / min, the speed of the high-speed disperser head is set to 18000r / min, the pulping time is set to 20min, and the temperature is set to 15℃±1℃; then the slurry is transferred to the grinder, the speed of the grinding rod is set to 3.1m / s, 0.03mm diameter zirconium dioxide grinding beads are selected, the pulping time is set to 20min, and the temperature is set to 1 5℃±1℃; then the slurry is transferred to a tank-type constant temperature ultrasonic disperser for ultrasonic dispersion, the ultrasonic power is set to 750W, the ultrasonic frequency is set to 20kHZ, the dispersion time is set to 20min, and the temperature control is set to 15℃±1℃; after the slurry is prepared through the dispersion steps of "slurrying-grinding-ultrasonic dispersion", the particle diameter of the slurry is detected by a nanoparticle size analyzer. If the particle diameter of the slurry meets the process requirements, the next step of spraying is carried out; if the particle diameter of the slurry does not meet the process requirements, the steps of "slurrying-grinding-ultrasonic dispersion" must be repeated; further, the process requirement for the slurry particle diameter is D 50 The particle diameter is ≤1μm, D 90 The particle diameter is ≤2μm, D 99 The particle diameter is ≤2.4μm; where D 50 Indicates the particle diameter when 50% of the particles are accumulated, D 90 Indicates the particle diameter when 90% of the particles are accumulated, D 99 Indicates the particle diameter when 99% of the particles are accumulated;

[0137] After the slurry has gone through the steps of "slurrying-grinding-ultrasonic dispersion" and the particle diameter of the slurry meets the particle size requirements, it is sprayed on the M765.08 composite proton exchange membrane to prepare each sub-catalytic layer; the thickness of the anode sub-catalytic layer A1 is 1μm; the thickness of the cathode sub-catalytic layer C1 is 2μm; the thickness of the cathode sub-catalytic layer C2, C3 and the anode sub-catalytic layer A2 is 3μm; the mass fraction of the slurry for preparing each sub-catalytic layer is 1.7%; the solvent of the slurry is isopropanol and ultrapure water, and the volume ratio of isopropanol and ultrapure water is 4:1; the platinum content of the catalyst is 40%, and the carrier content is 60%; the mass ratio of the ion polymer resin to the carrier is 0.65:1; the catalyst carrier and the ion polymer of each slurry are different in hydrophilicity and hydrophobicity to form a gradient hydrophobicity design; the thickness of each sub-catalytic layer is controlled by the spraying parameters;

[0138] First, the M765.08 proton exchange membrane was fixed on the bottom fixture with tape. The tension of the proton exchange membrane was controlled at 0.5-1N / m to prevent the deformation of the proton exchange membrane caused by the volatilization of the slurry solvent during the preparation of the sub-catalytic layer. After the proton exchange membrane was fixed, the top fixture was closed on the bottom fixture, and the spraying area of ​​the proton exchange membrane was set to 273cm by the fixture. 2 ;

[0139] The preparation of each sub-catalytic layer is completed by a sprayer; the preparation order of each sub-catalytic layer is "C1, C2, C3, A1 and A2", and the spraying parameters of each sub-catalytic layer are listed in Table 6;

[0140] Table 6 Spraying parameters of each sub-catalytic layer

[0141]

[0142] After the steps of preparing the sub-catalytic layers C1, C2, C3, A1 and A2 on the M765.08 proton exchange membrane are completed, the preparation of the 3CCM is completed;

[0143] The embodiment of the present application selects carbon fiber paper with bimodal pore size distribution, and performs zoned hydrophobic treatment on the carbon fiber paper to prepare for the subsequent preparation of the gas diffusion layer; the embodiment of the present application performs gas-liquid zoned transmission design and gradient pore size design on the base layer and microporous layer of the gas diffusion layer respectively to solve the gas-liquid dynamic transmission compatibility of the gas diffusion layer; the gas-liquid zoned transmission of the base layer is "using a hydrophobic agent with a specific particle diameter to perform hydrophobic treatment on the carbon fiber paper with bimodal pore size distribution to prepare a base layer with hydrophilic and hydrophobic zones; the carbon fiber paper with bimodal pore size distribution has a large pore size of 5μm to 20μm, a small pore size of 30nm to 60nm, and the pore volume inside the carbon fiber paper accounts for 86.7% of the total volume of the material, such as Figure 2 As shown in the table, in the “pore size (μm)-specific pore volume (cm 3In the "distribution diagram of carbon fiber paper (wt. / g)", the pore size of carbon fiber paper shows a bimodal distribution. According to the pore size characteristics of the large and small pores of carbon fiber paper, a polytetrafluoroethylene hydrophobic agent with a particle size distribution range of 0.1μm to 0.3μm is selected to perform hydrophilic and hydrophobic partitioning treatment on the carbon fiber paper to prepare the base layer.

[0144] First, a 60% polytetrafluoroethylene hydrophobic agent emulsion was diluted to a 20% emulsion; then the carbon fiber paper was immersed in the 20% polytetrafluoroethylene hydrophobic agent emulsion for 24 hours; a 273 cm 2 The carbon fiber paper is completely and horizontally immersed in the dilute emulsion, the depth of the dilute emulsion is 10mm, and the length and width of the cross section of the dilute emulsion are 10mm larger than the length and width of the carbon fiber paper; due to the limitation of the pore size of the carbon fiber paper, the polytetrafluoroethylene particles of a certain size can enter the micron-sized pores of the carbon fiber paper, making these areas highly hydrophobic; they cannot enter the nano-sized pores of the carbon fiber paper, making these areas relatively weakly hydrophobic; at low current density (less water is generated, close to 0.1A / cm 2 ), the weakly hydrophobic areas of the nanopores help retain the liquid, thereby providing better wettability and liquid transfer, avoiding excessive water loss in the catalyst layer adjacent to the substrate layer, and maintaining the proton transport capacity of the catalyst layer; at high current density (more water is generated, close to 1.8 A / cm 2 ), the strongly hydrophobic areas of the micron-sized macropores help to repel liquids, thereby optimizing gas diffusion and liquid water transmission; under full current density conditions, the substrate layer prepared in the embodiment of the present application can realize the partitioned transmission of liquid hydration reaction gas, avoiding interference caused by the opposite transmission directions of the two; most of the pores in the substrate layer are through holes, and the transmission power of liquid water is mainly provided by the capillary force of the pores. When pores of different pore sizes are connected through water, due to the difference in pore size, an additional capillary force difference from small pores to large pores will be generated to drive the liquid water to be transmitted to the large pores;

[0145] When the carbon fiber paper is impregnated, the carbon fiber paper is taken out and placed in a drying oven for vacuum drying to remove the dilute emulsion solvent adsorbed on the carbon fiber paper; the drying temperature is 80°C, the drying time is 4h, and the drying vacuum is 10Pa; when the carbon fiber paper is dried, the carbon fiber paper is taken out and placed in a high temperature box at 380°C for 10min, and protected by a nitrogen atmosphere. At this time, the temperature in the high temperature box is higher than the melting point of the polytetrafluoroethylene particles, and the polytetrafluoroethylene particles will melt and bond to the fibers of the carbon fiber paper, while removing the residual solvent to form a firm base layer. At this point, the base layer preparation for the cathode gas diffusion layer is completed, which is recorded as MPS C , MPS represents the substrate, and C represents the cathode;

[0146] After the hydrophobic treatment is completed, the MPS selected in the embodiment of the present application is measured using a porosity measuring instrument. C The porosity was characterized and the results showed that: MPS C The internal pore volume accounts for 78.1% of the total volume of the material; since the water content of the cathode of the fuel cell is relatively high and the water content of the anode is relatively low, the substrate used as the cathode gas diffusion layer needs to be strongly hydrophobic, and the substrate used as the anode gas diffusion layer needs to be weakly hydrophobic;

[0147] First, a 60% polytetrafluoroethylene hydrophobic agent emulsion was diluted to a 10% emulsion; then the carbon fiber paper was immersed in the 10% polytetrafluoroethylene hydrophobic agent emulsion for 12 hours; a 273 cm 2 The carbon fiber paper is completely and horizontally immersed in the dilute emulsion with a depth of 5 mm in the dilute emulsion, and the length and width of the cross section of the dilute emulsion exceed the length and width of the carbon fiber paper by 10 mm; when the carbon fiber paper is impregnated, the carbon fiber paper is taken out and placed in a drying oven for vacuum drying to remove the dilute emulsion solvent adsorbed on the carbon fiber paper; the drying temperature is 80°C, the drying time is 4 hours, and the drying vacuum is 10Pa; when the carbon fiber paper is dried, the carbon fiber paper is finally taken out and placed in a high-temperature box at 350°C for 10 minutes, and protected by a nitrogen atmosphere. At this time, the temperature in the high-temperature box is higher than the melting point of the polytetrafluoroethylene particles, and the polytetrafluoroethylene particles will melt into a fiber phase and bond to the fibers of the carbon fiber paper. At the same time, the residual solvent is removed, and a firm base layer will be formed. At this time, the preparation of the base layer used as the anode gas diffusion layer is completed, which is recorded as MPS A , A represents anode;

[0148] After the hydrophobic treatment is completed, the MPS selected in the embodiment of the present application is measured using a porosity measuring instrument. A Porosity characterization was performed, and the results showed that: MPS A The internal pore volume accounts for 81.4% of the total volume of the material; due to MPS C and MPS A The different PTFE impregnation conditions of MPS lead to different amounts of PTFE adsorbed in the internal pores, resulting in different porosities. C The PTFE loading rate is about 30%, MPS A The PTFE loading rate is about 25%;

[0149] The embodiments of the present application use different porous carbon materials (conductive carbon black XC72, carboxylated multi-walled carbon nanotubes and graphite sheets) to prepare a microporous layer with a gradient pore size on a substrate layer; based on the fact that the cathode catalyst layer of the fuel cell contains relatively more water and the anode catalyst layer contains relatively less water, the microporous layer of the cathode gas diffusion layer and the microporous layer of the anode gas diffusion layer are designed with a gradient pore size respectively; the microporous layer of the cathode gas diffusion layer connected to the cathode catalyst layer is designed to be divided into three sub-microporous layers, while the microporous layer of the anode gas diffusion layer connected to the anode catalyst layer is designed to be two sub-microporous layers; the transmission power of water in the microporous layer is mainly provided by capillary pressure, and for pores with the same hydrophobicity, the capillary pressure is mainly determined by the pore size; and most of the pores in the microporous layer are through holes. When pores of different pore sizes are connected through water, the difference in pore size will cause an additional capillary pressure difference from the small pore size pore to the large pore size pore, so as to drive Water is transported to the large-aperture pores; a capillary pressure difference in the macroscopic direction will be formed in the microporous layer, which improves the drainage capacity under high current density vehicle-mounted conditions, thereby reducing the transmission resistance of the reaction gas; the microporous layer with a gradient pore size structure not only forms an overall additional capillary pressure difference between the layers; inside the layers, the carboxylated multi-walled carbon nanotube layer and the graphite sheet layer also have a capillary pressure difference formed by the different pore sizes; this pressure difference drives the relatively evenly distributed liquid water transmitted from the conductive carbon black VXC72 layer to redistribute in the carboxylated multi-walled carbon nanotube and graphite sheet layers, converge to the large pores, and be transmitted to the next layer through the capillary pressure difference between the layers; at the same time, a large number of small-aperture pores have reduced internal water saturation, which reduces the gas transmission resistance, and the gas is more inclined to diffuse inward through the small-aperture pores, naturally forming a gas-liquid two-phase diversion; in addition, the gradient pore size microporous layer structure effectively inhibits the appearance of cracks in the microporous layer;

[0150] The microporous layer structure with gradient pore size and the partitioned hydrophobic treatment of the carbon fiber paper with bimodal pore size distribution designed in the embodiment of the present application improve the gas diffusion layer at low current density (less water is generated, close to 0.1A / cm 2 ) water retention capacity and high current density (more water is generated, close to 1.8A / cm 2 ) drainage capacity; compatible with the reaction gas diffusion and product water transmission under dynamic vehicle conditions, thereby improving the performance of the fuel cell, especially the discharge stability of the fuel cell under high power;

[0151] Example embodiment 2:

[0152] Based on the exemplary embodiment 1, the exemplary embodiment 2 is to respectively form a cathode substrate MPS C and anode substrate MPS A preparing a microporous layer with gradient pore sizes;

[0153] Cathode gas diffusion layer GDL CThe preparation method is as follows: conductive carbon black XC72, polytetrafluoroethylene and ultrapure water are dissolved and dispersed in polyethylene glycol monooctylphenyl ether (TritonX-100) emulsion; further, m(XC72):m(polytetrafluoroethylene):m(ultrapure water)=4:1:40, and the concentration of non-ionic surfactant TritonX-100 emulsion is 30%; after preparation, it is placed in a tank-type constant temperature ultrasonic dispersant for ultrasonication for 30 minutes, and the temperature is set to 15°C±1°C; after ultrasonic dispersion, it is placed in a magnetic stirrer and stirred at a speed of 90r / min for 2 hours to obtain the first microporous layer slurry, recorded as MPL S1 ;

[0154] Take carboxylated multi-walled carbon nanotubes, polytetrafluoroethylene and ultrapure water and dissolve and disperse them in polyethylene glycol monooctylphenyl ether (TritonX-100) emulsion; further, m (carboxylated multi-walled carbon nanotubes): m (polytetrafluoroethylene): m (ultrapure water) = 4:1:40, and the concentration of non-ionic surfactant TritonX-100 emulsion is 30%; after the preparation is completed, put it into a tank-type constant temperature ultrasonic dispersant for ultrasonication for 30 minutes, and the temperature is set to 15°C ± 1°C; after the ultrasonic dispersion is completed, put it into a magnetic stirrer and stir it at a speed of 90r / min for 2h to obtain the second microporous layer slurry, recorded as MPL S2 ;

[0155] Graphite flakes, polytetrafluoroethylene and ultrapure water are dissolved and dispersed in a polyethylene glycol monooctylphenyl ether (TritonX-100) emulsion; further, m (graphite flakes): m (polytetrafluoroethylene): m (ultrapure water) = 4:1:40, and the concentration of the non-ionic surfactant TritonX-100 emulsion is 30%; after the preparation is completed, it is placed in a tank-type constant temperature ultrasonic dispersant for ultrasonication for 30 minutes, and the temperature is set to 15°C ± 1°C; after the ultrasonic dispersion is completed, it is placed in a magnetic stirrer and stirred at a speed of 90r / min for 2 hours to obtain the third microporous layer slurry, recorded as MPL S3 ;

[0156] The carbon material loading of the cathode gas diffusion layer is the mass of carbon material loaded per unit area of ​​the substrate layer. S1 、MPL S2 and MPL S3 ) and the area of ​​the substrate layer are determined, the height of the scraper is set and the thickness of each microporous layer slurry is controlled, so that the total carbon material loading of the gas diffusion layer can be controlled to 1.6 mg / cm 2 To distinguish the positions of the sub-microporous layers on the substrate layer, the sub-microporous layers are named as the first microporous layer MPL1, the second microporous layer MPL2 and the third microporous layer MPL3 in order from the direction away from the substrate layer to the direction close to the substrate layer, that is, "MPL S1 Corresponding to MPL1, MPLS2 Corresponding to MPL2, MPL S3 Corresponding to MPL3";

[0157] MPS in the cathode basal layer C The preparation process of the microporous layer with gradient pore size is as follows:

[0158] First, use a scraper to first apply the microporous layer slurry MPL S3 MPS coated on the base layer C The surface was dried at room temperature for 4 hours and then placed in a muffle furnace for two-stage heat treatment; the first stage heat treatment temperature was 280°C, the first stage heat treatment time was 30 minutes, the second stage heat treatment temperature was 350°C, the second stage heat treatment time was 60 minutes, the heating rate was 5°C / min, and after the second stage heat treatment was completed, it was cooled to room temperature in the furnace to obtain a third microporous layer, recorded as MPL3;

[0159] Then use a scraper to first apply the microporous layer slurry MPL S2 Coated on the surface of MPL3, dried at room temperature for 4 hours, and then placed in a muffle furnace for two-stage heat treatment; the first stage heat treatment temperature is 280°C, the first stage heat treatment time is 30 minutes, the second stage heat treatment temperature is 350°C, the second stage heat treatment time is 60 minutes, the heating rate is 5°C / min, and after the second stage heat treatment is completed, it is cooled to room temperature in the furnace to obtain a second microporous layer, recorded as MPL2;

[0160] Then use a scraper to first apply the microporous layer slurry MPL S1 Coated on the surface of MPL2, dried at room temperature for 4 hours, and then placed in a muffle furnace for two-stage heat treatment; the first stage heat treatment temperature is 280°C, the first stage heat treatment time is 30 minutes, the second stage heat treatment temperature is 350°C, the second stage heat treatment time is 60 minutes, the heating rate is 5°C / min, and after the second stage heat treatment is completed, it is cooled to room temperature in the furnace to obtain the first microporous layer, recorded as MPL1;

[0161] During the preparation of the sub-microporous layers of the cathode gas diffusion layer, a heat treatment is performed after each microporous layer is prepared to avoid a large amount of mixing or interpenetration of the components between adjacent sub-microporous layers and to ensure the independence of the structure of each sub-microporous layer; that is, GDL C Mechanical structure: MPS C -MPL3-MPL2-MPL1, i.e. completion of cathode gas diffusion layer GDL C Preparation of

[0162] Anode gas diffusion layer GDL A The preparation method is as follows: first, use a scraper to spread the microporous layer slurry MPL S2 MPS coated on the base layer AThe surface was dried at room temperature for 4 hours and then placed in a muffle furnace for two-stage heat treatment; the first stage heat treatment temperature was 280°C, the first stage heat treatment time was 30 minutes, the second stage heat treatment temperature was 350°C, the second stage heat treatment time was 60 minutes, and the heating rate was 5°C / min. After the second stage heat treatment, it was cooled to room temperature in the furnace to obtain the third microporous layer, recorded as MPL2;

[0163] Then use a scraper to spread the microporous layer slurry MPL S1 Coated on the surface of MPL2, dried at room temperature for 4 hours, and then placed in a muffle furnace for two-stage heat treatment; the first stage heat treatment temperature is 280°C, the first stage heat treatment time is 30 minutes, the second stage heat treatment temperature is 350°C, the second stage heat treatment time is 60 minutes, the heating rate is 5°C / min, and after the second stage heat treatment is completed, it is cooled to room temperature in the furnace to obtain a second microporous layer, recorded as MPL1;

[0164] During the preparation of the anode gas diffusion layer, a heat treatment is performed after each microporous layer is prepared to avoid a large amount of mixing or interpenetration of the components between adjacent sub-microporous layers and to ensure the independence of the structure of each sub-microporous layer; that is, the anode gas diffusion layer GDL is completed. A Preparation of GDL A Mechanical structure: MPS A -MPL2-MPL1;

[0165] In order to characterize the microstructure of each sub-microporous layer (MPL3, MPL2 and MPL1) separately, the cathode gas diffusion layer was prepared in MPS C Sample 3, sample 2 and sample 1 were prepared respectively; the structure of sample 3 is MPS C -MPL3, the structure of sample 2 is MPS C -MPL2, the structure of sample 1 is MPS C -MPL1; According to the preparation method of the anode gas diffusion layer in MPS A Sample 2' and sample 1' were prepared separately; the structure of sample 2' is MPS A -MPL2, the structure of sample 1' is MPS A -MPL1;

[0166] The microscopic morphology of sample 3, sample 2, sample 1, sample 2' and sample 1' were characterized by scanning electron microscopy. Figure 3 As shown in part (c), the microporous layer of sample 3 is constructed by graphite sheets with a particle size of about 20 μm, irregular shape and obvious lamellar structure on the surface; the carboxylated multi-walled carbon nanotube microporous layers of samples 2 and 2' are as shown in Figure 3As shown in part (b), the outer diameter ranges from 40nm to 60nm, and the length is 0.5μm to 2μm. The carboxylated multi-walled carbon nanotubes are interconnected, intertwined, and interlaced with each other, forming a variety of structural and rich pores; the conductive carbon black microporous layer of sample 1 and sample 1' is shown in Figure 3 As shown in part (a), the conductive carbon black is a spherical particle with a diameter of about 30 nm. By combining different carbon materials (conductive carbon black, carboxylated multi-walled carbon nanotubes and graphite sheets), a microporous layer with a pore size gradient can be constructed.

[0167] For the microporous layer of the cathode gas diffusion layer, a carboxylated multi-walled carbon nanotube layer is placed between the conductive carbon black layer and the graphite sheet layer in the microporous layer of the three-layer structure, and the pore size distribution characteristics of the carboxylated multi-walled carbon nanotubes are utilized to obtain a microporous layer with a gradual pore size from large to small in the direction from close to the substrate layer to far away from the substrate layer, and the pore size of each sub-microporous layer changes more slowly, with a smaller gradient and a better degree of gradual change;

[0168] For the microporous layer of the anode gas diffusion layer, a carboxylated multi-walled carbon nanotube layer and a conductive carbon black layer are used together in the microporous layer of the two-layer structure, and the pore size distribution characteristics of the carboxylated multi-walled carbon nanotubes are utilized to weaken the hydrophobicity of the microporous layer, which is beneficial to compatibility with the anode gas diffusion and the relatively small water content of the anode;

[0169] The transmission power of liquid water in the microporous layer is mainly provided by the capillary force of the pores. Most of the pores in the microporous layer are through holes. When the pores of different sizes in the microporous layer are connected by water, due to the difference in pore size, additional capillary force will be generated in the direction from the small-diameter pores to the large-diameter pores, so as to drive the liquid water to be transmitted into the large-diameter pores; additional capillary force in the vertical in-plane direction will be formed in each sub-microporous layer, which will enhance the drainage capacity of the gas diffusion layer under high current density, thereby reducing the reaction gas transmission resistance of the gas diffusion layer under high current density;

[0170] The gas diffusion layer prepared in the embodiment of the present application, on the one hand, forms a gradient pore size between each sub-microporous layer, which brings additional capillary force in the vertical direction in the plane, and on the other hand, the bimodal distribution of the pore size in the substrate layer also provides additional capillary force in the plane; this driving force will cause the liquid water transmitted from the microporous layer to converge to the macropores of the substrate layer, and the small pores of the substrate layer have a reduced water saturation, which reduces the reaction gas transmission resistance, and the gas is more inclined to diffuse to the catalyst layer through the pores with small pores, while the liquid product water is discharged from the macropores to the bipolar plate flow channel, and finally the amount of liquid water carried away is controlled by the flow rate of the reaction gas;

[0171] The embodiment of the present application forms a favorable gas-liquid two-phase split inside the gas diffusion layer through material selection of the substrate layer, hydrophobic treatment and gradient pore size design of the microporous layer, which can effectively improve the reaction gas diffusion capacity and liquid water transmission capacity of the gas diffusion layer, thereby improving the discharge stability under high current density conditions; the embodiment of the present application balances the two-phase transmission of reaction gas and liquid water through structural innovation of the gas diffusion layer;

[0172] Regarding the on-board dynamic working conditions, under low current density working conditions, the fuel cell produces less water, and the small pore area with weak hydrophobicity will attract the product water from the catalyst layer. Since the water in the small pores is not saturated and the drainage rate is slow, a part of the liquid water will be retained, forming a weak drainage state under low power working conditions. At this time, the reaction gas mainly diffuses through the large pores, and the product water is discharged through the small pores; under high current density working conditions, the fuel cell produces more water, the water in the small pores will be saturated and transfer liquid product water to the large pores. The large pores are highly hydrophobic and have a faster liquid water transmission rate, forming a strong drainage state under high power working conditions; at this time, the reaction gas diffuses through the small pores, and the water is discharged through the large pores;

[0173] Example embodiment 3:

[0174] Exemplary embodiment 3 prepares a membrane electrode based on exemplary embodiments 1 and 2; the present embodiment adopts a UV curing glue process to prepare a membrane electrode; completes 3CCM, GDL C and GDL A After the preparation, the membrane electrode is packaged; the membrane electrode frame is packaged with polyethylene naphthalate, and one side of the polyethylene naphthalate is pre-coated with a layer of ultraviolet curing glue with a thickness of 5 μm; the total thickness of the single-piece sealing frame is 100 μm ± 2 μm;

[0175] First, GDL C Place it in the center of the cathode side of the 3CCM, and then use 2mm wide tape to tape the GDL C Fix it on the cathode side of 3CCM to get 4CCM; then take a cathode sealing frame, with the UV curing glue side facing the cathode catalyst layer side, and align the inner edge of the cathode sealing frame with the GDL C Align and fix the cathode side sealing frame to the GDL with 2mm wide tape. C Then turn the 5CCM over, take a piece of anode side sealing frame, with the UV curing glue side facing the anode catalyst layer side, align the outer edges of the two sealing frames to get 6CCM; finally, GDL A Place it in the center of the anode side of the 6CCM and align it with the inner edge of the anode sealing frame. Then use 2mm wide tape to tape the GDL. AFix it on the sealing frame on the anode side to obtain 7CCM; after the layered assembly is completed, irradiate the sealing frame on the anode side of 7CCM with an ultraviolet lamp for 30 seconds; after the anode irradiation is completed, turn over 7CCM, and irradiate the sealing frame on the cathode side of 7CCM with an ultraviolet lamp for 30 seconds;

[0176] The main functions of the membrane electrode sealing frame are to protect the proton exchange membrane, enhance the sealing performance of the membrane electrode, enhance the mechanical properties of the membrane electrode and prevent excessive compression of the gas diffusion layer. It should be pointed out that the materials of the cathode side sealing frame and the anode side sealing frame are the same, but the positions are different; after the 7CCM is prepared, the 7CCM is cut with a cutting die to remove the excess material on the sealing frame to obtain the membrane electrode;

[0177] Fifth, illustratively, the embodiment of the present application uses TA1 commercial pure titanium to prepare the cathode plate and the anode plate; the cathode plate flow field adopts a straight-through cross-variable flow field, and the anode plate flow field adopts a corrugated constant cross-section flow field;

[0178] The specific strength of TA1 commercially pure titanium is 3.5 times that of 316L stainless steel, which allows TA1 commercially pure titanium to greatly reduce the weight of the fuel cell stack while ensuring the strength of the bipolar plate, making it very suitable for fuel cell passenger car applications;

[0179] The cathode flow field adopted in the embodiment of the present application is a straight-through cross-variable flow field; the flow channel of the straight-through cross-variable flow field first has the advantages of a straight-through flow channel: the reaction gas pressure loss is relatively small, the current density distribution is relatively uniform, the reaction gas in the flow channel enters the gas diffusion layer by diffusion, and the reaction gas pressure difference between the parallel flow channels is relatively small; the inlet and outlet distances of a single straight flow channel are relatively close, and the product hydration reaction heat in each flow channel can be carried out of the flow channel by the reaction tail gas; secondly, the flow channel of the straight-through cross-variable flow field has some narrow variable diameter nodes, and the variable diameter nodes of adjacent flow channels are cross-distributed. The cross-sectional area of ​​this flow channel along the air flow direction periodically increases and decreases, It can increase the disturbance of air and force part of the air into the membrane electrode. This flow channel structure will generate a pressure gradient, which is more conducive to the discharge of product water in the flow channel, and further reduce the concentration polarization of the stack; in the direction perpendicular to the flow channel, the diameter-changing node of the first flow channel is located in the middle section of the conventional structure of the second flow channel. The diameter-changing node is a high-pressure area, and the conventional structure is a low-pressure area. When the air pressures of adjacent areas in the flow field are different, the air in the high-pressure area will cross the ridge of the bipolar plate and enter the low-pressure area under the pressure. This forced convection can bring out the heat of the liquid hydration reaction under the ridge of the bipolar plate, preventing the gas diffusion layer under the ridge from being flooded and the membrane electrode from overheating;

[0180] The advantages of the straight-through cross-variable flow field adopted in the embodiment of the present application are: first, it strengthens the diffusion of air from the bipolar plate to the membrane electrode, and improves the utilization rate of air; second, it strengthens the mass transfer of air between the bipolar plate flow channels, and enhances the transmission efficiency of the product hydration reaction heat under the bank ridge; finally, it increases the flow rate of air in the flow channel, which is more conducive to removing the product hydration reaction heat in the flow channel; the straight-through cross-variable flow field can balance oxygen diffusion, drainage under the bank ridge, heat transfer under the bank ridge and air pressure loss; combined with the flow control of the air subsystem and the temperature control of the hydrothermal subsystem, the water management ability of the straight-through cross-variable flow field for dynamic vehicle conditions is controlled;

[0181] The anode flow field adopted in the embodiment of the present application is a corrugated constant cross-section flow field; when hydrogen flows through the bend of the corrugated constant cross-section flow field, Dean vortices will be formed, thereby changing the steady flow state of hydrogen, greatly enhancing the convection of hydrogen, strengthening the diffusion of hydrogen from the bipolar plate to the membrane electrode, and improving the utilization rate of hydrogen; the Dean vortex can improve the ability of hydrogen exhaust to transfer heat while avoiding hydrogen turbulence. At the same time, since the corrugated constant cross-section flow channel will intersect with the coolant flow channel, the intersection part can make the hydrogen flow channel contact with several coolant flow channels, further improving the temperature control ability of the hydrothermal subsystem on the anode flow field and reducing the hysteresis of temperature control; the advantages of the corrugated constant cross-section flow field adopted in the embodiment of the present application are: first, the Dean vortex can improve the ability of hydrogen exhaust to discharge liquid water while avoiding hydrogen turbulence; secondly, combined with the flow control, pressure control of the hydrogen subsystem and the temperature control of the hydrothermal subsystem, the water management ability of the corrugated constant cross-section flow field for dynamic vehicle conditions is improved;

[0182] Example embodiment 4:

[0183] Since the forming performance and elastic modulus of TA1 commercial pure titanium are lower than those of 316L stainless steel, the present embodiment adopts a magnetic pulse incremental forming process based on a uniform pressure coil to prepare cathode flow fields (such as Figure 4 ) and the anode flow field (as Figure 6 shown);

[0184] The channel dimensions of the cathode flow field are: channel depth 0.35mm, channel conventional structure width 1.1mm, channel conventional structure length 10mm, channel variable diameter node width 0.55mm, channel variable diameter node length 1mm, the chamfer between the channel conventional structure and the variable diameter node is 135°, and the distance between each channel is 1mm; the dimensions of the anode flow field are: channel depth 0.3mm, channel width 1mm, distance between each channel is 1mm, rotation angle 45°, and linear length of the circulation unit is 10mm;

[0185] The present application embodiment uses an EMF-20 magnetic pulse forming machine to stamp the cathode plate and the oxygen electrode plate. The schematic diagram of the forming part is shown in FIG. Fig.11As shown; the equipment parameters of the magnetic pulse forming machine are: storage energy 20kJ, energy storage capacitor 100μF, rated voltage 0~20kV; the bottom pressure plate and side support plate of the fixed frame of the magnetic pulse forming machine play a positioning role and provide bottom support, and the top pressure plate is fixed by fastening bolts; the forming part of the magnetic pulse forming machine includes "cathode die or anode die, conductive channel, coil, coil skeleton, die seat, drive plate and pad", etc.; the coil is placed inside the conductive channel, the TA1 pure titanium workpiece and the drive plate are placed above the die, and the pad is placed in the grooves on both sides of the die; the spacing between the die and the TA1 pure titanium workpiece is set to 2mm; in order to minimize the possibility of electrical breakdown, the exposed parts of the screw, support plate and wire, and the contact area between the bottom of the edge block and the drive plate are wrapped with insulating tape, At the same time, the side walls of the conductive channel are isolated with 3240 epoxy resin plates. Before discharge, in order to reduce the problem of electrical contact, the conductive channel area in contact with the drive plate is coated with conductive silver glue. With the support plates of different thicknesses, the clamping force of the fastening bolts is reasonably adjusted. The forming part is placed in the frame. During forming, the force on the drive plate directly acts on the TA1 pure titanium workpiece. A 9kV low-voltage three-pass discharge forming method is used to progressively form a 0.1mm thick TA1 pure titanium workpiece at an acceleration distance of 2mm and driven by a 0.3mm thick copper drive plate. Two discharge areas are respectively formed in a continuous discharge mode to achieve multi-pass forming. The TA1 pure titanium workpiece is progressively formed by magnetic pulses using a cathode die to form a cathode plate, and the TA1 pure titanium workpiece is progressively formed by magnetic pulses using an anode die to form an anode plate.

[0186] After the cathode plate and the anode plate are prepared, the embodiment of the present application adopts laser welding to prepare the bipolar plate; the bipolar plate has a three-cavity structure, namely, an oxygen flow field on the cathode side, a hydrogen flow field on the anode side, and a cooling liquid cavity in the middle; the laser welding line is a conductive structure to electrically connect the cathode plate and the anode plate;

[0187] Sixth, after completing the laser welding of the bipolar plate, the bipolar plate needs to be surface treated to improve the conductivity and surface hydrophobicity of the bipolar plate and ensure the adhesion of the surface coating; the embodiment of the present application adopts magnetron sputtering combined with vacuum heat treatment to prepare a nano C / TiC composite coating on the surface of the TA1 bipolar plate, that is, to complete the surface treatment of the bipolar plate;

[0188] The nano C / TiC composite coating consists of a carbon surface layer and a TiC middle layer. The structure of the nano C / TiC composite coating is as follows: Figure 8 As shown; the experimental data show that the nano C / TiC composite coating can effectively improve the conductivity and hydrophobicity of the bipolar plate, and due to the presence of the TiC intermediate layer, the bond between the carbon layer and the titanium substrate is more solid;

[0189] Example embodiment 5:

[0190] First, the TA1 bipolar plate was immersed in a 5% volume fraction hydrofluoric acid solution for 30 seconds to remove the oxide layer on the surface of the TA1 bipolar plate; then the TA1 bipolar plate was placed in a tank ultrasonic cleaning machine, the cleaning solution was deionized hydrated ethanol, and the cleaning time was 15 minutes to remove the impurities remaining on the TA1 bipolar plate, and the plate was dried at room temperature after ultrasonic cleaning; then the TA1 bipolar plate was placed in a vacuum chamber of the deposition system, and the vacuum chamber was evacuated to a pressure of ≤0.001Pa; then pure argon gas was introduced into the vacuum chamber, and the pressure was maintained at 0.5Pa; a DC power supply was applied to a graphite target (purity 99.99%) to deposit a single layer of carbon on the TA1 bipolar plate; the TA1 bipolar plate was etched for 15 minutes by ion bombardment with a negative bias of 300V and a current of 2A to further remove the oxide layer on the surface of the TA1 bipolar plate;

[0191] Finally, a negative bias of 400V and a current of 3A were applied to the graphite target to prepare a monolayer of carbon on the surface of the TA1 bipolar plate, which was maintained for 2000s. During the deposition of the monolayer of carbon, the gas flow rate of argon was 40sccm and the duty cycle of argon was 20%. The magnetron sputtering current refers to the current intensity passing through the graphite target, which affects the thickness and uniformity of the carbon coating. The magnetron sputtering negative bias refers to the voltage applied to the graphite target, which is conducive to providing sufficient potential difference to promote the release of carbon atoms from the surface of the graphite target and deposit them on the TA1 substrate to form a carbon coating, affecting the sputtering effect and the quality of the carbon coating. The magnetron sputtering time is the holding time after applying the magnetron sputtering negative bias and magnetron sputtering current, which affects the quality and performance of the carbon coating.

[0192] After the carbon surface layer is prepared on the TA1 bipolar plate, the TA1 bipolar plate is heat treated; the TA1 bipolar plate is sealed in an oxygen-free quartz tube, and the quartz tube is placed in a muffle furnace and heated to 700°C for 210 seconds; the "C / TiC nanocomposite coating" is completed; the heat treatment time and heat treatment temperature affect the thickness of the titanium carbide interface layer;

[0193] Comparative Example 1:

[0194] In order to characterize the improvement of conductivity and hydrophobicity of TA1 commercial pure titanium by C / TiC nanocomposite coating and eliminate the interference of cathode flow field or anode flow field on the characterization test; TA1 commercial pure titanium was cut into small pieces of 30mm×30mm×0.1mm; firstly, TA1 commercial pure titanium was immersed in 5% volume fraction hydrofluoric acid solution for 30s to remove the oxide layer on the surface of TA1 commercial pure titanium; then TA1 commercial pure titanium was placed in a tank ultrasonic cleaning machine, the cleaning solution was deionized hydrated ethanol, and the cleaning time was 15 minutes to remove the impurities remaining on TA1 commercial pure titanium, and dried at room temperature after ultrasonic cleaning; then TA1 commercial pure titanium was placed in the vacuum chamber of the deposition system, and the vacuum chamber was evacuated to a pressure of ≤0.001Pa; then pure argon gas was introduced into the vacuum chamber, and the pressure was maintained at 0 .5Pa; using magnetron sputtering technology, a DC power supply is applied to a graphite target (purity 99.99%) to deposit a single layer of carbon on TA1 commercial pure titanium; TA1 commercial pure titanium is etched for 15 minutes by ion bombardment with a negative bias of 300V and a current of 2A to further remove the oxide layer on the surface of TA1 commercial pure titanium; finally, a negative bias of 400V and a current of 3A are applied to the graphite target to prepare a single layer of carbon on the surface of TA1 commercial pure titanium for 2000s; during the deposition of the single layer of carbon, the gas flow rate of argon is 40sccm, and the duty cycle of argon is 20%, so as to obtain a single layer of carbon coating; after the deposition of the single layer of carbon coating, the TA1 commercial pure titanium is sealed in an oxygen-free quartz tube, and the quartz tube is placed in a muffle furnace and heated to 700°C for 210s, thus completing the "C / TiC nanocomposite coating";

[0195] The contact resistance test was performed on the C / TiC nanocomposite coating prepared on the surface of TA1 commercial pure titanium in the embodiment of the present application, and the test results of the contact resistance are listed in Table 7;

[0196] Table 7 Test results of contact resistance

[0197]

[0198] The contact resistance measurement results show that the contact resistance of the C / TiC nanocomposite coating is only ; The contact resistance of the naturally generated passivation layer of TA1 commercial pure titanium is as high as ; This shows that the C / TiC nanocomposite coating can effectively improve the conductivity of TA1 commercial pure titanium and avoid the formation of a passivation film on the surface of TA1 commercial pure titanium;

[0199] The water contact angle test was performed on the C / TiC nanocomposite coating prepared on the surface of TA1 commercial pure titanium in the embodiment of the present application, and the test results of the water contact angle are listed in Table 8;

[0200] Table 8 Test results of water contact angle

[0201]

[0202] The measurement results of water contact angle show that after a layer of C / TiC nanocomposite coating is deposited on TA1 commercial pure titanium by magnetron sputtering, the water contact angle of TA1 commercial pure titanium can be increased from 81° to 127° through surface treatment; this shows that the C / TiC nanocomposite coating can effectively improve the hydrophobicity of TA1 commercial pure titanium and enhance the water management ability of the self-humidifying fuel cell system under high current density conditions;

[0203] The corrosion resistance of the C / TiC nanocomposite coating prepared on the surface of TA1 commercial pure titanium in the embodiment of the present application was tested, and the test results of the corrosion resistance are listed in Table 9;

[0204] Table 9 Corrosion resistance test results

[0205]

[0206] The results of corrosion current measurements show that after a layer of C / TiC nanocomposite coating was deposited on TA1 commercial pure titanium by magnetron sputtering, it has the same corrosion resistance as the passivation layer.

[0207] Example embodiment 6:

[0208] First, 330 membrane electrodes were prepared according to exemplary embodiment 1, exemplary embodiment 2, and exemplary embodiment 3; 335 surface-treated TA1 bipolar plates were prepared according to exemplary embodiment 4 and exemplary embodiment 5, and silicone rubber wires were pasted on the bipolar plates to obtain 335 "bipolar plate assemblies";

[0209] Then, 4 pseudo-single cells were prepared; 8 rectangular sealing frames were taken and cut out according to the length and width of 7CCM; the sealing frames were placed in pairs and irradiated with ultraviolet light to prepare 4 "double sealing frames" from the 8 sealing frames; the "double sealing frames" were cut with a membrane electrode cutting die to obtain 4 pseudo-single cells with the same outer contour size as the membrane electrode;

[0210] After the preparation of membrane electrode, bipolar plate assembly and pseudo-cell is completed, the stack is assembled; the stack adopts a U-shaped layout, that is, the air inlet and air outlet are located on the same side of the stack; the stack is compressed and assembled according to "pressure end plate / insulating plate / current collecting plate / bipolar plate assembly / pseudo cell 1 / bipolar plate assembly / pseudo cell 2 / battery cell / pseudo cell 3 / bipolar plate assembly / pseudo cell 4 / bipolar plate assembly / current collecting plate / insulating plate / inlet end plate", and the compression rate of the stack is set to 20%; among them, the battery cell is the core part of the stack, which is composed of 330 membrane electrode and 331 bipolar plate assemblies stacked in sequence; 2 pseudo-cells are placed at the air inlet and blind ends of the stack respectively to alleviate the inconsistency of the stack temperature and humidity caused by the head-end effect;

[0211] Optimizing the control strategy of the auxiliary system can timely discharge excess liquid product water, including "the water thermal management subsystem controls the operating temperature of the fuel cell stack, the air subsystem controls the air flow, the hydrogen subsystem controls the hydrogen flow, and the auxiliary heat dissipation subsystem controls the air inlet temperature";

[0212] Among them, the operating temperature of the stack is the coupling point of multiple physical fields, involving the amount of reverse diffusion water, the water content of the proton exchange membrane λ, the electroosmotic drag coefficient n, and the gas-phase water ratio of the stack; within the design framework of the embodiment of the present application, the proton exchange membrane will have the largest amount of reverse diffusion water in the Gore-selsect series, a moderate membrane water content (λ=11~15), and a moderate electroosmotic drag coefficient (n=1.4~2.5), which can achieve self-consistent balance of membrane electrode product water;

[0213] Example embodiment 7:

[0214] First, Example 6 prepared a stack containing 330 membrane electrodes, each with an effective area of ​​273 cm 2 , there are two pseudo single cells at the beginning and end of the stack; then according to Fig. 9 To build a self-humidifying fuel cell system; the operating parameters of the fuel cell system are shown in Table 10; wherein, at each current density point, in order to maintain the force balance of the proton exchange membrane, the hydrogen pressure value and the air pressure value are equal;

[0215] Table 10 Fuel cell system operating parameters

[0216]

[0217] Within the design framework of the embodiment of the present application, the rated power of the self-humidifying fuel cell system is 130 kW; the upper power limit is 125 kW, the lower power limit is 3 kW, the loading slope is 8 kW / s, and the unloading slope is 12 kW / s; the total capacity of the lithium-ion battery is (20 A·h), the upper limit of the lithium-ion battery SOC is 80%, the lower limit of the lithium-ion battery SOC is 60%, and the initial SOC of the lithium-ion battery is 50%; the charging power of the self-humidifying fuel cell system for the lithium-ion battery is 40 kW; the current density of the self-humidifying fuel cell system is limited to 0.1 A / cm by the VCU 2 ~1.8A / cm 2 Within the operating window;

[0218] ① Estimate the maximum discharge power that the lithium-ion battery can currently release based on the current SOC of the lithium-ion battery:

[0219] Maximum discharge power = [(lithium-ion battery open circuit voltage - port voltage for one second of discharge) × port voltage for one second of discharge] / discharge resistance;

[0220] ② Estimate the maximum charging power that the lithium-ion battery can currently absorb based on the current SOC of the lithium-ion battery:

[0221] Maximum charging power = absolute value [(lithium-ion battery open circuit voltage - maximum allowable port voltage) × maximum allowable port voltage / charging resistance]

[0222] ③Define the deviation coefficient α:

[0223] α=[0.5×(SOC max +SOC min )-SOC re ] / [0.5×(SOC max -SOC min )]

[0224] Limit the range of α to -1 to 1;

[0225] ④Residual supplementary power of the self-humidifying fuel cell system:

[0226] When α ≥ 0, the fuel cell system does not need to supplement the surplus power;

[0227] When α<0, the fuel cell system supplements the remaining power value as “the smaller of A value and B value”;

[0228] A value = bus feedback power - the maximum charging power that the lithium-ion battery is currently estimated to be able to absorb

[0229] B value = deviation coefficient × lithium-ion battery charging power

[0230] In summary, regarding the self-humidifying fuel cell system, the embodiment of the present application first optimizes the whole vehicle energy pipeline strategy of the VCU, and reasonably allocates the power size and direction of each energy source (fuel cell system, lithium-ion battery) of the hybrid system, so that the fuel cell system works in the self-humidifying operation window of the embodiment of the present application (as shown in Table 10); secondly, the proton exchange membrane is selected to increase the amount of water diffused in the reverse direction and alleviate the water imbalance between the anode and cathode; and thirdly, the components of the membrane electrode (gradient hydrophobic catalyst layer, substrate selection and hydrophobic treatment, microporous layer gradient pore size regulation) are selected, designed and optimized to achieve the membrane electrode internal Precise management of water in the fuel cell stack; then, the flow field of the bipolar plate is selected, the flow direction of the reaction gas and the hydrophobicity of the coating are optimized, and the hydrogen subsystem, air subsystem and water-heat management subsystem are strengthened to precisely control the hydrogen flow rate, air flow rate and operating temperature of the fuel cell stack. At the same time, the water content of the hydrogen intake and the water content of the air intake in the fuel cell stack are optimized by the hydrogen circulation pump, gas-liquid separator and intercooler to reduce the peak and fill the valley, so as to keep the water content in the fuel cell stack at a reasonable level; at the height of the entire fuel cell system, a self-consistent balance of product water is established at each current density point to realize the self-humidification function of the fuel cell system;

[0231] Compared with the traditional fuel cell system, the self-humidifying fuel cell system designed in the embodiment of the present application removes the humidification module (humidifier, auxiliary pipelines and auxiliary valves) of the air subsystem, which greatly reduces the complexity of the fuel cell; and the embodiment of the present application adopts titanium bipolar plates to reduce the weight of the fuel cell system itself, making it more suitable for passenger car applications, and also reflects the future development direction of the fuel cell industry - miniaturization and lightweight;

[0232] The embodiments of the present application select, design, optimize and improve "selection of proton exchange membrane, gradient hydrophobicity design of catalyst layer, selection and hydrophobic treatment of (gas diffusion layer) substrate layer, gradient pore size design of (gas diffusion layer) microporous layer, selection of bipolar plate material and flow field, bipolar plate coating design, optimization of auxiliary system control strategy and improvement of vehicle energy management" to achieve the self-humidification function of the fuel cell system; at the same time, by removing the humidification module (humidifier, auxiliary pipes, auxiliary valves, etc.) in traditional technology and using titanium bipolar plates, the compact and lightweight design of the self-humidifying fuel cell is achieved, making it more suitable for the application scenarios of passenger cars.

[0233] The above embodiments are only used to illustrate the technical methods of the embodiments of the present application and are not intended to limit them. Although the embodiments of the present application have been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical methods of the embodiments of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical methods of the embodiments of the present application.

Claims

1. A self-humidifying fuel cell hybrid power system suitable for a passenger car, characterized in that: Including lithium-ion battery units, fuel cell units and vehicle controllers; The fuel cell unit comprises a fuel cell stack, a hydrogen subunit and an air subunit, wherein the air subunit does not contain a humidification module; the fuel cell stack comprises a membrane electrode comprising a proton exchange membrane; The system achieves self-wetting of the proton exchange membrane by controlling the current density and temperature of the stack; The number and size of membrane electrodes in the stack are adapted to the power requirements of the on-board operating conditions of the passenger car to meet the self-wetting of the proton exchange membrane. The vehicle controller is used to manage the hybrid power output of the fuel cell unit and the lithium-ion battery unit. The current density range of the stack that achieves self-wetting of the proton exchange membrane is called the current density window; the current density window value range is 0.1-1.8A / cm 2 ; The temperature range of the stack that achieves self-wetting of the proton exchange membrane is called the temperature window; the value range of the temperature window is 65-80°C; The thickness of the proton exchange membrane is 6-10 μm; the numerical range of the ion exchange equivalent of the proton exchange membrane is 790-1075 g / mol; the effective area of ​​the stack is 273 cm 2 330 sections of membrane electrode.

2. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 1, characterized in that: The membrane electrode also includes a catalyst layer and a gas diffusion layer; the catalyst layer has a gradient hydrophobicity, and the hydrophobicity of the catalyst layer increases in sequence in the direction away from the proton exchange membrane; the gas diffusion layer has a base layer, and the small pores and large pores on the base layer are bimodal distribution; the small pores and large pores are connected pores, the large pores are micron-level pores with strong hydrophobicity, and the small pores are nanometer-level pores with weak hydrophobicity; a microporous layer with a gradient pore size distribution is prepared on the base layer of the gas diffusion layer to form a derivative structure with gradient hydrophobicity.

3. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 1, characterized in that: The battery stack also includes a bipolar plate, which is made of pure titanium and is progressively formed based on a uniform voltage coil magnetic pulse to form a cathode flow field and an anode flow field, and is laser welded; a graphite carbon surface layer is provided on the surface of the bipolar plate, and a nano C / TiC composite coating is formed on the graphite carbon surface layer in combination with vacuum heat treatment.

4. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 3, characterized in that: The cathode flow field in the bipolar plate adopts a straight-through cross-variable flow field; the anode flow field in the bipolar plate adopts a corrugated constant cross-section flow field.

5. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 1, characterized in that: The vehicle controller is used to manage the hybrid power output of the fuel cell unit and the lithium-ion battery unit, including: the vehicle controller performs the hybrid power output of the fuel cell unit and the lithium-ion battery unit through a power following strategy. The power following strategy is that the vehicle controller adjusts the power distribution of the fuel cell system and the lithium-ion battery according to the bus power demand of the vehicle and the charge state of the lithium-ion battery, and mainly uses the fuel cell to meet the power demand of the load, and the difference is supplemented or absorbed by the lithium-ion battery, so that the fuel cell system works in the best efficiency range; the best efficiency range is [lower power limit, upper power limit], and the method for determining the lower power limit and the upper power limit is: According to the "power-efficiency" characteristic curve of the fuel cell unit, the optimal efficiency value is determined by considering the mass flow rate of hydrogen, and the power lower limit and power upper limit of the fuel cell unit are determined when the optimal efficiency value decays by 10% to 15%.

6. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 5, characterized in that: The lithium-ion battery unit presets an upper limit value SOC of the lithium-ion battery state of charge SOC max and the lower limit of SOC SOC min , the target value SOC of the lithium-ion battery state of charge SOC mid It is the median of the upper limit value of the state of charge SOC of the lithium-ion battery and the lower limit value of the SOC; By detecting the real-time value of the state of charge (SOC) of the lithium-ion battery re , estimate the maximum discharge power that the lithium-ion battery cell can currently release and the maximum charging power that it can currently absorb; Lithium-ion battery state of charge SOC real-time value SOC re The deviation coefficient α is obtained using the following formula: α=[0.5×(SOC max +SOC min )-SOC re ] / [0.5×(SOC max -SOC min )], By limiting -1≤α≤1, the load slope and unloading efficiency of the fuel cell unit, the charging power of the lithium-ion battery unit, and the initial value of the state of charge SOC of the lithium-ion battery unit are set.

7. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 6, characterized in that: The power following strategy includes: (1) when the power demand of the bus exceeds the maximum power that the lithium-ion battery can currently release, the fuel cell unit is turned on; (2) when the real-time value SOC of the lithium-ion battery at the current moment is re Less than or equal to the lower limit of SOC min , the fuel cell unit is turned on; (3) During regenerative braking, the feedback power of the bus is greater than the current SOC real-time value SOC of the lithium-ion battery re The corresponding charging demand, the fuel cell unit shuts down; (4) During regenerative braking, the feedback power of the bus is less than the current SOC real-time value SOC of the lithium-ion battery re Corresponding to the charging demand, the fuel cell unit supplements the remaining power; (5) If the bus demand power is less than the fuel cell unit power, the bus charges the lithium-ion battery; (6) If the bus demand power is greater than the fuel cell unit power, the lithium-ion battery unit releases power to the bus.

8. The self-humidifying fuel cell hybrid power system suitable for a passenger car according to claim 7, characterized in that: The fuel cell unit supplements the remaining power in the following ways: (a) When α ≥ 0, the fuel cell unit does not need to supplement the surplus power; (b) When α<0, the residual power value supplemented by the fuel cell unit is "the smaller of A and B". A is the difference between the bus feedback power and the maximum charging power that the lithium-ion battery is currently estimated to be able to absorb. B is the product of the SOC deviation coefficient α and the charging power of the lithium-ion battery. (c) When SOC re <SOC min , and the supplementary surplus power value is between the power lower limit and the power upper limit of the fuel cell unit. At this time, the supplementary surplus power value is the power upper limit of the fuel cell unit. At the same time, the loading slope and unloading slope of the supplementary surplus power value meet the slope limit requirements.

Citation Information

Patent Citations

  • Microporous layer structure of fuel cell and preparation method therefor, and fuel cell cathode assembly

    CA3080007A1

  • Starting and testing method for fuel cell stack without external humidification

    CN112993334A